Non-Gaussian fatigue analysis of packaged fruit under random vibration using an improved CEEMDAN hybrid Gaussian decomposition approach - Song-Ping Yang; Jun-Ye He; He-Mu Yu; Tong Ji; Zhi-Wei Wang (Postharvest Biology and Technology, 2026)

Comparative structural, colloidal, and kinetic evaluation of yeast, soy, and whey proteins: uncovering the modification needs of yeast protein - Siliang Wu; Kewei Chen; Wen Li; Xueying Song; Yihan Mu; Mouming Zhao; Guowan Su (Food Hydrocolloids, 2026)

Persulfate-assisted anaerobic digestion systems: advances in microbial electron transport chain reconstruction and metabolic regulation driven by reactive oxygen species - Yingjin Song; Sheng Xu; Yanshan Wang; Lan Mu; Huiling Niu; Qingyi Li; Yinjie Zhong; Yvxing Luo; Zhi Wang; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

Synergetic piezo‐photocatalytic tuning internal electric field in S-scheme heterojunction for highly efficient tetracycline degradation and hydrogen production - Shiyu Song; Xinyue Yan; Jiandong Zhu; Yazi Liu; Lei Wang; Feihu Mu; Huan He; Qiuyi Ji; Shaogui Yang (Water Research, 2026)

Nationwide occurrence and site-scale dynamics of antibiotics in landfill-associated waters in China - Lin Mu; Fusheng Zha; Menghe Wen; Qiao Wang; Xiaojin Song (Water Research, 2026)

Advances in MOF-enabled food preservation and packaging: A critical review of structure-function relationships, functionalization strategies, applications, and safety - Yinghua Tang; Yuqin Feng; Xuefeng Liu; Kuiran Liu; Wenhua Mu; Yating Song; Yuqing Duan; Guishan Liu (Food Research International, 2026)

Unlocking the antioxidant potential of wheat gluten: structural transitions and peptide release driven by ultrasonication-assisted pH shifting - Peng Cheng; Xueying Song; Yihan Mu; Siliang Wu; Mouming Zhao; Guowan Su (Food Chemistry, 2026)

Electrospun nanofiber interfaces for aquatic products preservation: spoilage microenvironments, molecular interactions, and mechanism-oriented design strategies - Kuiran Liu; Yuqin Feng; Xuefeng Liu; Yinghua Tang; Wenhua Mu; Yating Song; Yuqing Duan; Guishan Liu (Food Bioscience, 2026)

Engineering an “nano-antibiotic”: Synergistic catalytic bacterial killing via metal-phenolic network accelerating Fe(III)/Fe(II) cycle on MIL-101(Fe) - Qin Zhang; Xiaoming Song; Yifan Zhou; Lulu Pan; Xuemin Mu; Xiaolin Wang; Yanyan Li; Xiuhua Zhao (Chemical Engineering Journal, 2026)

Photoperiod induces alterations in redox homeostasis, immune response, and responses to light stimulation in the red swamp crayfish (Procambarus clarkii) - Lang Zhang; Qi Bai; Yingchun Mu; Yali Yu; Liting Ye; Lu Qiao; Wenya Ji; Jie Peng; Meiping Lan; Ziwei Song; Yu Fang (Aquaculture, 2026)

Asymmetric hydrodynamic modeling and identification for a twin-pod-propelled ship: Dalian Maritime University’s Xin Hongzhuan - Lei Zhang; Dongdong Mu; Guofeng Wang; Yunsheng Fan; Baojian Song (Ocean Engineering, 2026)

Manganese-amended constructed wetlands coupled with microbial fuel cells significantly enhance methane mitigation: synergistic mechanisms of electrochemical source suppression and manganese-mediated terminal oxidation - Lingyun Mu; Wenjuan Zhai; Xinshan Song; Yunkun Qian; Zhongshuo Xu; Wei Huang (Journal of Environmental Chemical Engineering, 2026)

Permafrost degradation amplifies infrastructure-related inequalities across the Qinghai-Tibet Plateau - Xinlong Du; Chunling Zhang; Yunjie Jia; Yuguo Wei; Jinyue Song; Mei Mu; Xiaoqing Peng; Zongxing Li; Peng Zhang; Lin Liu; Zhuoxuan Xia; Rongkun Liu; et al. (Global Environmental Change, 2026)

Sustainable bio-aerogels for food packaging applications: Fabrication strategies, preservation mechanisms, and innovation trends - Xuefeng Liu; Yuqin Feng; Yating Song; Jiajun Guo; Kuiran Liu; Yinghua Tang; Wenhua Mu; Jianfang Li; Yuqing Duan; Guishan Liu (Food Research International, 2026)

A Systematic Survey and Geoconservation Strategy for Geoheritage Resources in the Guang’an Region, Southwest China - Sibao Zhu; Hong-Xu Mu; Zizheng Wang; Qingwei Song; Minghui Li; Qing Zhou; Jun Liu; Bangguo Zhou; Canhai Jin (Geoheritage, 2026)

Investigation, Evaluation and Geoconservation of the Yardang Landforms in Dahaidao Region, Hami Basin, Xinjiang, NW China - Qing-Wei Song; Hong-Xu Mu; Zhao-Jie Chen; Xu-Dong Song; Xiu-Long Zhang; Ying Dong; Yi-En Xiao (Geoheritage, 2026)

Silicon addition mitigates nitrogen-induced reduction in community stability by increasing species asynchrony, species richness and dominant species stability - Wenhong Zhou; Danghui Xu; Zhengwei Ren; Yuqi Wu; Baiyin Huang; Wenbo Mu; Zhaoliang Song; Wei Mu; Yawen Gui (Acta Oecologica, 2026)

External electronic effect enhances room-temperature phosphorescence and photochromism in organophosphine oxide - Zhuke Gong; Xiudan Song; Jianhui Sun; Ruotong Ma; Qingfeng Mu; Yuanting Guo; Xiaojun Zhang; Hui Xu (Science Bulletin, 2026)

Nitric acid-modified co-pyrolyzed biochar from gentamicin mycelial residue and biomass regulates cattle manure composting: Reducing carbon loss and enhancing humification - Yingjin Song; Huiling Niu; Yamei Zeng; Guanyi Chen; Zeng Dan; Beibei Yan; Lan Mu; Yuxing Luo; Yinjie Zhong; Sheng Xu; Qingyi Li; Anna Jin (Journal of Environmental Management, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Striking a balance: Grain yield and functional substances of black rice (Oryza sativa L.) under shading stress in tropical regions - Shaokun Song; Song Li; Zongli Liu; Yixue Mu; Long Chen; Heng Zhang; Kaiwen Qiu; Lixiao Nie (European Journal of Agronomy, 2026)

Laser-processed biomimetic hydrogel patches with tunable bio-adhesion, muscle tissue regeneration, and synergistic antibacterial activity - Luxing Wei; Jun Huang; Yingwen Mu; Liuguang Song; Yi Yu; Yuquan Wang; Gexing Peng; Ningji Gong; Jian Shen (Chemical Engineering Journal, 2026)

Aging-Related Changes in the Injury Response of the Peripheral Nervous System - Yue-Yan Cen; Mu-Yun Wang; Qin-Xuan Song; Xin-Lin Gao; Cheng Zhou; Chun-Jie Li; Fei Liu; Yan-Yan Zhang; Jie-Fei Shen (Neuroscience Bulletin, 2026)
Peripheral nerve injury (PNI) significantly impairs patients’ quality of life, with elderly individuals experiencing particularly severe consequences due to aging-related declines in neuronal injury response and repair capabilities. Processes of the generation and transmission of injury signals, axonal disruption, initiation of regeneration, and the elongation of regenerating axons, as well as the subsequent reinnervation by these axons, are all significantly influenced by aging. These alterations are closely associated with changes in mitochondrial function, neuronal transport systems, a persistent inflammatory milieu, and various microenvironmental non-neuronal cells. Therefore, this review synthesized the pivotal role of aging in the multifaceted regulation of the nervous system following PNI and highlighted promising molecular regulatory mechanisms in the signaling pathways. Furthermore, it identified critical areas for future research, including unresolved questions in age-associated injury responses, potential targets for pharmacological intervention, and emerging therapeutic strategies meriting consideration for research and development.

Characterization and mechanistic insights into changes in flavor compounds of yeast extract during the evaporative process - Yuting Liu; Siliang Wu; Xueying Song; Yihan Mu; Mouming Zhao; Guowan Su (Innovative Food Science & Emerging Technologies, 2026)

Grain quality, texture characteristics, and starch fine structure of ratoon rice practiced with high stubble height: Insights from panicles regenerated at different stem nodes - Wanfeng An; Mingji Yu; Ruixue Yu; Shuiyin Yang; Jiali Miao; Qingyao Huang; Jizhe Mu; Jianquan Qin; Chang Zheng; Xiaoyan Song; Quanzhi Zhao (Food Research International, 2026)

Decoding novel umami peptides from soy protein isolate hydrolysate: Mechanistic insights via multisensory techniques, machine learning and molecular docking - Xueying Song; Dipeng Mei; Yihan Mu; Peng Cheng; Siliang Wu; Chenchen Cao; Guowan Su (Food Bioscience, 2026)

Exopolysaccharides from Lactiplantibacillus plantarum Y12 enhance adhesion to HT-29 cells and gastrointestinal survival, and act synergistically with Y12 to alleviate DSS-induced colitis in mice by modulating the gut microbiota and repairing the intestinal barrier - Xiaochen Shi; Tianhao Zhang; Xueqi Lu; Meichen Sui; Zhiyan Wen; Yanfeng Tuo; Guangqing Mu; Yinglong Song (Food Bioscience, 2026)

A tree location optimization via metamodel-based simulation framework for mitigating extreme heat in communities - Yuhong Bai; Wangshu Mu; Changqing Song (Computers, Environment and Urban Systems, 2026)

Development and application of KASP molecular marker for accelerated breeding of low-acid Cerasus humilis cultivars - Xia-Yu Xing; Xiao-Yan Wang; Yue-Zhan Xiao; Hao-Nan Wang; Hou-Qiang Song; Ming Liu; Xiao-Peng Mu; Jian-Cheng Zhang; Lu-Ting Jia; Yu Gary Gao; Shuai Zhang; Peng-Fei Wang (Plant Cell Reports, 2026)

Spatiotemporal patterns of bacterial communities and their responses to environmental gradients in a river–reservoir system - Yuhai Zhuo; Nan Li; Bobo Liu; Jianwu Li; Anli Song; Hao Mu; Fei Zhang; Xiang Liu; Zhi Yang; Tinglin Huang; Hongxi Zheng (Antonie van Leeuwenhoek, 2026)

Acid-base imbalance electrolytic cell (AB-EC) for efficient treatment of acid mine drainage (AMD): Metal recovery and hydrogen production - Haoyang Song; Zhudi Chen; Jinyuan Jiang; Wei Tan; Zhaocong Ren; Mu Feng; Dongni Shi; Hongke Qin; Lei He; Xiaojun Pan; Kuk Cho (Journal of Environmental Chemical Engineering, 2026)

Predictive Multi-Physics coupling coal combustion model under rapid heating - Hanjian Li; Ying Zhao; Shichen Ding; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Huanying Chi (Fuel, 2026)

Mixing and stratification dynamics shape bacterial community composition, assembly patterns, and co-occurrence networks in Han River cascade reservoirs - Hao Mu; Haihan Zhang; Jianwu Li; Anli Song; Bobo Liu; Yuhai Zhuo; Fei Zhang; Xiang Liu; Tinglin Huang; Nan Li; Hongxi Zheng (Environmental Research, 2026)

Narrowing the green emission of CsPbBr3 quantum dot glass via high fluorine doping strategy toward backlit displays - Xinhao Cai; Shaojun Wang; Anjun Huang; Yingzhu Zi; Yan Mu; Yuhuan Li; Yue Liu; Yangke Cun; Farhod Shokir; Zhiguo Song; Jianbei Qiu; Daqin Chen; et al. (Chemical Engineering Journal, 2026)

In-plane macro/meso-porous structured MXene film constructed by in situ solvothermal etching method with superior capacitive performance - Yesheng Wang; Leling Song; Jixin Wang; Dandan Zhu; Jinghua Wang; Yanbiao Ren; Dan Mu; Yanxin Yu (Chemical Engineering Journal, 2026)

Comparative Analysis of Growth Patterns and Sexual Dimorphism of Scylla paramamosain in Pond Culture - Jiahui Liu; Ronghua Li; Yang Jiang; Yun Hu; Zhuang Li; Qingyang Wu; Changkao Mu; Weiwei Song; Chunlin Wang; Ce Shi (Fishes, 2026)
To investigate the growth patterns and sexual differences in pond-cultured mud crabs (Scylla paramamosain), this study measured eight growth patterns in pond-cultured S. paramamosain aged 1 to 5 months, including internal carapace width (ICW), abdomen width (AW), body height (BH), carapace length (CL), propodus length (PL), merus length (ML), first periopod merus length (1PML), and body weight (BW), with measurements taken monthly. The growth patterns for females, males, and a mixed-sex group were fitted using the following three growth curve models: Logistic, Gompertz, and von Bertalanffy. The fitting results indicate that the optimal growth model for male S. paramamosain is the Logistic model, while the optimal growth model for female S. paramamosain is the von Bertalanffy model. The predicted growth inflection points and inflection weight for male S. paramamosain are 3.15 months and 155.00 g, respectively; for female S. paramamosain, the predicted growth inflection point and inflection weight are 4.25 months and 228.71 g, respectively; and for mixed-sex S. paramamosain, the growth inflection point and inflection weight are 3.22 months and 151.80 g, respectively. Males achieve a rapid growth period earlier (at 3–4 months of age) than females, with the weight of male crabs significantly greater than that of females at four months of age (p

Corrigendum to ‘ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection’ [Pesticide Biochemistry and Physiology 220 (2026) 107056] - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

An infant-derived Bifidobacterium pseudocatenulatum DPU-MWF3-6 strain exhibits favorable in vitro functional properties and is well tolerated during early life in neonatal rats - Zhao Zhang; Yanchen Liu; Fanhua Kong; Yinglong Song; Yaowei Liu; Xiaomeng Wu; Guangqing Mu (Food Bioscience, 2026)

Intercalation-mediated bionic nano-hydrogel adhesives for robust omni-domain adhesion - Jialve Sun; Zhengzhi Mu; Tianye Yang; Hexuan Yu; Wenda Song; Zhiyan Zhang; Junqiu Zhang; Shichao Niu; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2026)

A Systematic Review of the Application of Chinese Satellite Observations for Water Quality Remote Sensing - Bingqian Han; Muhammad Bilal; Muhammad Usman; Meng Mu; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Chong Fang; Sijia Li; Shidi Shao; Yang Li; et al. (Chinese Geographical Science, 2026)

Synergistic metabolism between Veillonella ratti and Lactobacillus acidophilus and its inhibition of enterohemorrhagic Escherichia coli infection in piglet - Wenhui Zheng; Yi Hao; Hejing Wang; Yuxin Han; Wenchao Song; Yanan Mu; Tianjia Feng; Zhaoyu Zhang; Bianfang Liu (Archives of Microbiology, 2026)

Biological control of a novel strain Bacillus velezensis BFWR11 against tomato early blight - Yuxin Han; Wenhui Zheng; Yanan Mu; Tianjia Feng; Yi Hao; Wenchao Song; Jin Cai; Boting Zhan; Zhaoyu Zhang; Bianfang Liu (Antonie van Leeuwenhoek, 2026)

Species-dependent growth rates regulate community biomass under long-term warming and wetting in alpine meadow on the Qinghai-Tibet Plateau - Mingming Shi; Cuicui Mu; Bingrong Zhou; Xiaodong Li; Yunqiao Ma; Mei Mu; Jinyue Song; Xinlong Du; Huakun Zhou (Plant and Soil, 2026)

Global Fixed-Time Path-Following Control with Prescribed Performance for an Unmanned Surface Vehicle under Lumped Uncertainties and Input Saturation: Simulations and Experiments - Baojian Song; Yunsheng Fan; Dongdong Mu; Guofeng Wang; Peng Liu; Yaxuan Wang (Ocean Engineering, 2026)

Photoelectrotrophic denitrification and iron-sulfur-nitrogen cycle enhance nutrient removal in pyrite-amended constructed wetlands - Xiaoxiao Hou; Lingyun Mu; Yingying Liu; Yanping Xiao; Xinshan Song; Xiaoxiang Zhao; Dong An (Journal of Environmental Management, 2026)

Saccharomyces cerevisiae BR14 fermentation modulates volatile flavor profile of milk and enhances its protective efficacy against DSS-induced colitis in mice - Zhiyong Mu; Yijin Yang; Yongjun Xia; Xin Song; Lianzhong Ai (Food Bioscience, 2026)

Effect of Nitrogen and Maize Straw on Soil Nitrogen Transformation, Farm Profitability, and Wheat Yield: Balancing Productivity and Environmental Sustainability - Siddique Ahmad; Wenjing Song; Yanling Mu; Xiaobin Zhang; Shuping Xiong; Muhammad Arif; Muhammad Amjad; Laiba Urooj; Basit Ullah; Xinming Ma; Yihao Wei (Agricultural Research, 2026)

Design of robot navigation system under spatial constraints in shiitake mushroom fruiting room - Hualu Song; Kangkang Qi; Wenjie Feng; Yuanjie Mu; Jun Li; Xiangyu Lv; Zhichao Liang; Fengyun Wang (Computers and Electronics in Agriculture, 2026)

Enhancement of calcium oxide on hydrogen production and degradation of polylactic acid microplastics in anaerobic fermentation - Xiaoxuan Zhu; Ruirui Shang; Xi Yang; Chuanzheng Song; Hui Mu; Chunhui Zhao; Huanhuan Guo; Yongfang Zhang (Journal of Environmental Management, 2026)

Effect of CO2 and H2O on pyrolysis characteristics and structural evolution of Zhundong coal under rapid heating rate - Huanying Chi; Shichen Ding; Ying Zhao; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Hanjian Li (Fuel, 2026)

High-value utilization of hazardous solid waste for efficient electrocatalytic oxygen reduction to produce hydrogen peroxide - Bo Liu; Xiaoshuang Song; Guoxin Mu; Jiayu Feng; Fang Wang; Rui Cao; Zibin Pan; Feixiang Lu; Ping Ning; Shuo Cui; Lijuan Jia (Environmental Research, 2026)

Denitrification driven by varying concentrations of Mn (II) under no external carbon source conditions: Denitrification performance, nitrogen transformation and metabolic pathways - Lingyun Mu; Xiaoxiao Hou; Xinshan Song; Xiangzhou Meng; Dong An (Bioresource Technology, 2026)

First Report on the Asexual Morphology of Nigrograna jinghongensis (Nigrogranaceae, Pleosporales) with a New Host Record from China - Li‐Xue Mi; Hai‐Yan Song; Kevin D. Hyde; Prapassorn D. Eungwanichayapant; Ausana Mapook; Mu‐Sen Chen; Dian‐Ming Hu (New Zealand Journal of Botany, 2026)
Nigrograna jinghongensis was originally described based on sexual morphology from decaying woody litter in Yunnan Province, China. In this study, we report its asexual morph, isolated as endophytes from Tetradium ruticarpum in Anhui Province. The asexual morph of N. jinghongensis features coelomycetous pycnidia that are dark brown and globose to pyriform, bearing filiform, septate conidiophores with phialidic, hyaline conidiogenous cells, and ellipsoidal to subcylindrical, aseptate, guttulate conidia. Species identification was confirmed by multigene phylogenetic analysis using ITS, LSU, SSU, tef1‐α , and rpb2 sequences. This is the first report of the asexual morph of N. jinghongensis , expanding knowledge of its life cycle, ecological adaptability, and host association.

Effects of light spectrum on survival rate, growth performance, and oxidative stress in juvenile swimming crab (Portunus trituberculatus) - Lulu Zhu; Shuai Zhang; Shujian Chen; Changbin Song; Yangfang Ye; Ronghua Li; Weiwei Song; Changkao Mu; Chunlin Wang; Ce Shi (Journal of Oceanology and Limnology, 2026)

Joint topic entity and intent recognition model for multimodal agricultural diseases and pests question answering - Jingzhong Huang; Xia Hao; Yu Wang; Ruizhi Song; Zenan Mu; Sijie Niu; Xuchao Guo (Computers and Electronics in Agriculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Dual-readout digital colorimetric assay for zearalenone in corn based on alkaline phosphatase mediated growth of Prussian blue nanoparticles - Shanghong Ji; Tingtiao Pan; Weizhen Xu; Song Tang; Guodong Mu; Zeyu Hu; Yu Zhou (Food Chemistry, 2026)

Effects of farmland shelterbelts on water erosion at regional scale: a case study in the black soil region of Northeast China - Suhua Zhu; Xuan Mu; Xiao Zheng; Xingyi Li; Lining Song (Agroforestry Systems, 2026)

Investigation of the BMP signaling pathway in the swimming crab (Portunus trituberculatus) and its role in molting and growth - Huaihua Yu; Jinbiao Jiao; Yangfang Ye; Ce Shi; Chunlin Wang; Ronghua Li; Weiwei Song; Huan Wang; Congcong Hou; Changkao Mu (Aquaculture, 2026)

Annual variation in gonadal parameters and the effects of estradiol (E2) on ovarian development in the thick-shelled mussel, Mytilus coruscus - Leifeng Guo; Qianhui Cui; Ronghua Li; Zhongqi Gu; Ji Huang; Changkao Mu; Weiwei Song; Chunlin Wang (Aquaculture, 2026)

Spatial characterization and health risk evaluation of residual phenol five years after a river pollution incident - Tingting Liu; Fengjing Song; Yiming Sun; Zhen Ding; Hao Zheng; Shixuan Hao; Hong Xu; Yan Liu; Chao Wang; Xiaomin Xie; Mu Zhu; Peixuan Shen; et al. (Journal of Hazardous Materials, 2026)

Sensitivity analysis of design variables in semi-batch reverse osmosis for energy-efficient water treatment - Linyinxue Dong; Yumiao Song; Yuxuan Liu; Mo Xie; Dongyan Mu; Jungbin Kim (Journal of Cleaner Production, 2026)

An improved open-top dynamic chambers method for measuring the exchange fluxes of N2O, NO and NH3 from farmland - Minhang Tan; Yining Hu; Yifei Song; Zixuan Huang; Yujing Mu; Junfeng Liu; Chenglong Zhang; Pengfei Liu; Yuanyuan Zhang (Journal of Environmental Sciences, 2026)

Flexible dual-mode capacitive sensor based on snowflake-like flowable electrode and multi-level microstructured dielectric layer with long proximity sensing distance and high linear sensitivity - Yuxia Li; Wenzheng Song; Liangsong Huang; Peng Zhang; Liqun Yang; Zhichao Mu; Ranran Yang; Yuteng Tang (Chemical Engineering Journal, 2026)

Revealing dissolution process and mechanism of montmorillonite by two stereoisomers of malic acids and its effect on the Cr(III) retention properties: Insights from DFT simulations and experimental studies - Jingjie Yang; Li Zeng; Yong Wang; Song Liu; Aiqin Wang; Liang Bian; Temirlan Arslanov; Bin Mu; Hailiang Dong; Peng Liu; Xiaobin Gu (Chemical Engineering Journal, 2026)

Integration of AD and pyrolysis for char fertilizer: Pyrolysis and nutrient characteristics of biogas residue at different fermentation degrees - Lan Mu; Kongyue Li; Yifan Wang; Biyu Wang; Zhanjun Cheng; Yunan Sun; Yingjin Song; Guanyi Chen (Biomass and Bioenergy, 2026)

Phaeovulum Molybdatiresistens sp. nov., a Molybdate-resistant Bacterium Isolated from Eutrophic Pond Water - Jianjun Song; Yuanshuo Qiu; Ke Ma; Yuelin Liu; Jia Wang; Yaqi Liu; Xiaolong Song; Kaiyue Wang; Jinhua Hu; Weidong Mu; Yanfang Zhao; Aijv Liu; et al. (Current Microbiology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A parallel guidance and control method for path planning and collision avoidance of unmanned surface vehicles - Xiaojie Sun; Weidong Zhang; Dongdong Mu; Xiaona Song; Pengju Si; Yunsheng Fan (Ocean Engineering, 2025)

Refined evaluation of winter wheat drought and climate change implications - Junfang Zhao; Huiwen Peng; Yunkun Song; Jiaxin Wang; Jia Mu (Journal of Cleaner Production, 2025)

Comparison of compositional, structural, and functional characteristics in walnut (Juglans regia L.) proteins prepared from walnut meal: Effects of extraction and isolation methods - Yihan Mu; Xueying Song; Siliang Wu; Dongxiao Sun-Waterhouse; Geoffrey I.N. Waterhouse; Mouming Zhao; Guowan Su (Food Chemistry, 2025)

Grain yield and functional substance content in colored ratoon rice system under low solar radiation stress in southern China - Shaokun Song; Heng Zhang; Long Chen; Yixue Mu; Song Li; Ye Tao; Zaid Ulhassan; Haider Sultan; Lixiao Nie (Field Crops Research, 2025)

Multi-system toxicity of lead (Pb) in Procambarus clarkii: Integrated analysis of tissue damage, immune dysfunction, oxidative stress, and microbial dysbiosis via multi-omics approaches - Lang Zhang; Ziwei Song; Qiuying Qin; Li He; Juan Tian; Yali Yu; Yingchun Mu; Liqi Zhong; Zongbin Cui; Jinhua Gan (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Three-dimensional molecular engineering of fluorene-based self-assembled monolayers for high-performance inverted perovskite solar cells - Fen Xia; Xiaohan Lin; Jing Zhang; Jun Yin; Jing Li; Xijiao Mu; Song Tu; Binghui Wu; Nanfeng Zheng (Chemical Engineering Journal, 2025)

Elevated incubation temperature enhances the growth performance and increases the percentage of female offspring in the swimming crab, Portunus trituberculatus - Shurong Wu; Qingwei Chen; Ronghua Li; Run Tong; Chunlin Wang; Changkao Mu; Ce Shi; Weiwei Song (Aquaculture International, 2025)

Splicing factor Nova regulates the splice variants in exons 3 and 6 of GABA receptor subunit RDL from Chilo suppressalis Walker (Lepidoptera: Crambidae) - Zijiao Song; Jie Jiang; Tao Tang; Guanghua Luo; Junyan Wang; Kaixiang Lin; Lili Mu; Chunqing Zhao (Pesticide Biochemistry and Physiology, 2025)

Post-conversion vegetation restoration: PRE and VPD dominated the NDVI changes on the Loess Plateau - Hao Jia; Biqing Tian; Xiaoyan Song; Wenyi Sun; Xingmin Mu (Journal of Environmental Management, 2025)

Hydrochemical characteristics and circulation pattern of fault-type geothermal water in karst region: A case study in western Yunnan, China - Chuan Wen; Wenping Mu; Qiang Wu; Zhen Yang; Rong Li; Yubing Song; Hui Tan (Geothermics, 2025)

Comprehensive assessment of full-cycle high-solid anaerobic digestion of straw for methane production update: Focus on performance improvement and circular economy - Yingjin Song; Yinjie Zhong; Yanshan Wang; Lan Mu; Yuxing Luo; Sheng Xu; Huiling Niu; Zhi Wang; Beibei Yan; Guanyi Chen (Environmental Research, 2025)

Effects of β-hydroxy-β-methylbutyrate inclusion on growth performance and fillet quality of olive flounder Paralichthys olivaceus fed low fishmeal based diets - Chaoqing Wei; Zhenxia Su; Cancan Xia; Lu Li; Zhicheng Song; Hua Mu; Hanliang Cheng; Jianhe Xu; Zhiguo Dong; Binlun Yan; Lu Zhang (Aquaculture, 2025)

Hydrogen-rich reduction coupled with wet leaching for the conversion of spent SCR catalysts into carbide solid solutions - Rong Mu; Zepeng Lv; Shaolong Li; Jilin He; Jianxun Song (Journal of Environmental Chemical Engineering, 2025)

Dual-functionalized MIL-53-NH₂ MOFs for high-capacity and reversible ammonia storage: Synergistic effects of hydrogen bonding and electrostatic interactions - Lei Zhang; Guifeng Xiang; Lei Zhang; Ruikang Song; Ying Wang; Yidan Mu; Ziqing Liu (Journal of Environmental Chemical Engineering, 2025)

Integrated machine learning model for prediction of nutrients contents and maturity in rural organic solid wastes aerobic composting - Hao Peng; Lan Mu; Yingjin Song; Hong Su; Yadong Ge; Zhanjun Cheng; Rundong Li; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Emission fluxes of nitrous acid (HONO) from livestock and poultry wastes - Wenjin Zhang; Pengfei Liu; Min Song; Xuran Li; Xiaoxi Zhao; Yifei Song; Di Tian; Chenglong Zhang; Yuanyuan Zhang; Yangang Ren; Chengtang Liu; Junfeng Liu; et al. (Journal of Environmental Sciences, 2025)

Releasing ACE-inhibitory peptides from walnut protein via pulsed electric field: A multiscale mechanism-structure-function investigation - Xueying Song; Siliang Wu; Chenchen Cao; Yihan Mu; Ying Li; Ruili Liu; Guowan Su (Innovative Food Science & Emerging Technologies, 2025)

Water retention curves of a deformable lean clay under various stress ratios: Emphasizing the pore shape effects - Qing-yi Mu; Tian-qi Song; Chao Zhou; Jian-bing Peng (Computers and Geotechnics, 2025)

Breaking boundaries and collaborative symbiosis: Radical-nonradical-polymerization in persulfate advanced oxidation processes - Fuming Miao; Junsheng Song; Youzhi Liu; Yang Mu; Weizhou Jiao (Chemical Engineering Journal, 2025)

Tailoring key intermediates and interfacial water at Ag92Ru8 aerogel toward sustainable ammonia synthesis from nitrate - Junjie Chen; Xiaomei Xing; Sisi Wen; Mengyuan Li; Di Liu; Wenji Jiang; Xinyi Shao; Ruikai Qi; Yumei Yang; Ming Mu; Zheng-jie Chen; Bing Zhao; et al. (Chemical Engineering Journal, 2025)

Tissue-Selective Separation Mechanism of Multi-type Soft Tissues Under Waterjet Impact for Low-Trauma Cutting Surgery - Jiaqi Zhao; Xiao-Fei Song; Xiaoxian Wei; Jiuke Mu; Peng Peng; Wenli Yu (Annals of Biomedical Engineering, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Turanose and erlose as characteristic oligosaccharides in honey: Their formation mechanism and potential application for detecting honey adulteration - Sha Yan; Yuzhe Yuan; Huailei Song; Guodong Mu; Xiaofeng Xue (Food Chemistry, 2025)

Soybean protein isolate hydrolysate addition during fermentation of soybean meal with Aspergillus oryzae enhances the release of umami components in subsequent hydrolysis process - Yihan Mu; Hui Kang; Xueying Song; Chenchen Cao; Dongxiao Sun-Waterhouse; Geoffrey I.N. Waterhouse; Mouming Zhao; Guowan Su (Food Bioscience, 2025)

Multidirectional energy absorption of bionic multi-cell tubes inspired by bamboo phloem - Shuang Zhang; Wenda Song; Zhengzhi Mu; Zhiyan Zhang; Jingde Yang; Hexuan Yu; Wenzheng Wu; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2025)

Passenger-centric model predictive control for indoor temperature to facilitate energy-efficient airport terminal - Zhiwei Li; Zhuo Chen; Jili Zhang; Song Mu (Building and Environment, 2025)

Comparative analysis of rural organic waste treatment: greenhouse gas emissions, economics, and energy flow - Hao Peng; Lan Mu; Yingjin Song; Dan Zeng; Hong Su; Zhanjun Cheng; Rundong Li; Guanyi Chen (Biomass and Bioenergy, 2025)

Nitrogen uptake and nitrification in the Changjiang estuary - Xing Hou; Chongcong Liu; Guodong Song; Jinglong Mu; Wen Liang; Haoming Xu; Nian Wu; Wenqi Xu; Su Mei Liu (Marine Environmental Research, 2025)

Evaluating the contribution of residential coal combustion to atmospheric nitrous acid (HONO) in winter - Yang Wang; Pengfei Liu; Chenglong Zhang; Chaoyang Xue; Xiaoxi Zhao; Shuang Fu; Zichen Wu; Yifei Song; Yuzheng Wang; Chengtang Liu; Yujing Mu (Environmental Pollution, 2025)

MiR-30d-5p Modulates Glucose and Lipid Metabolism by Targeting CD73 through the AMPK Pathway - Mingjie Song; Juan Wang; Wenli Mu; Yanwei Zheng; Yanjun Cai; Jing Liu; Yu Xia (Cell Biochemistry and Biophysics, 2025)

Evaluation of nitrogen removal performance and metabolic mechanism of a novel salt-tolerant strain Pseudomonas aeruginosa SH3 - Yueyue Zhou; Xiaopeng Wang; Zhe Chen; Ce Shi; Shujian Chen; Lei Liu; Changkao Mu; Chunlin Wang; Weiwei Song (Bioresource Technology, 2025)

SLC39A10 is a key zinc transporter in T cells and its loss mitigates autoimmune disease - Yichang Shao; Qingdian Mu; Rong Wang; Hongbin Luo; Zijun Song; Pengfei Wang; Jingshu Song; Chaodong Ge; Jiyan Zhang; Junxia Min; Fudi Wang (Science China Life Sciences, 2025)

Microplastics and nanoplastics increase major adverse cardiac events in patients with myocardial infarction - Yun Zhang; Qianhui Gao; Qiang Gao; Mingcheng Xu; Ning Fang; Lin Mu; Xuejie Han; Hui Yu; Song Zhang; Yue Li; Yongtai Gong (Journal of Hazardous Materials, 2025)

Hydrogeochemical analysis and tracing of heavy metal contamination in groundwater using self-organizing mapping - Zhenzhou Sun; Qinghai Deng; Liping Zhang; Lusheng Song; Hongjuan Zhao; Jiutan Liu; Xiao Wu; Jiayi Mu (Environmental Geochemistry and Health, 2025)

Temporal transcriptome analysis provides molecular insights into night-time molting of juvenile mud crab (Scylla paramamosain) - Shujian Chen; Jiahao Liu; Ce Shi; Herve Migaud; Xuelin Zhao; Qingyang Wu; Yangfang Ye; Ronghua Li; Weiwei Song; Changkao Mu; Chunlin Wang (Aquaculture, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Sedimentary heavy metal interactions with phytoplankton and zooplankton across the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Environmental Management, 2025)

Fabrication of a high strength, swelling resistance, and conductive hydrogel for flexible underwater sensor via ketalization - Kejun Zhong; Jie Xiang; Yu Liu; Chuanlin Song; Yuetong Mu; Ting Yao; Kai Zhao; Tianfeng Gu; Pengxiang Jia; Wenyan Zhang (Chemical Engineering Journal, 2025)

Effect of on stereoisomers of lactic acids on microbially-mediated reductive dissolution of clay minerals: Insights from DFT and experimental studies - Jingjie Yang; Liang Bian; Aiqin Wang; Xiaofeng Zhao; Jianan Nie; Temirlan Arslanov; Bin Mu; Hailiang Dong; Mianxin Song; Li Zeng; Peng Liu; Xiaobin Gu (Applied Clay Science, 2025)

Diversity and dynamics of microbial communities during spontaneous fermentation of different cultivars of apples from China and their relationship with the volatile components in the cider - Jingyi Zhou; Xinyi Wang; Yonghao Cao; Yichao Cheng; Wenchao Li; Haibin Mu; Yanying Liang; Bin Tian; Xixi Zhao; Yuyang Song (Food Research International, 2025)

Probiotic potential of lactic acid bacteria with antioxidant properties in modulating health: Mechanisms, applications, and future directions - Yuan Gao; Qimeng Liang; Junqi Sun; Xiaomeng Wu; Yinglong Song; Yunpeng Xu; Hui Nie; Jun Huang; Guangqing Mu (Food Bioscience, 2025)

Molecular characterization of a novel non-segmented double-stranded RNA mycovirus isolated from the phytopathogenic fungus Lasiodiplodia pseudotheobromae - Zhengzhe Guan; Mengjiao Wang; Jiayi Ma; Mengyuan Mu; Xinyu Li; Peimeng Sun; Mengyuan Zhang; Yuanyuan Zhang; Luyang Song; Caiyi Wen; Ying Zhao (Archives of Virology, 2025)

Comparative Transcriptomic Analysis of Male and Female Gonads in the Zig-Zag Eel (Mastacembelus armatus) - Fangyu Cui; Yuanyuan Wang; Haiyan Liang; Yexin Yang; Zhiyong Jiang; Jiahuan Song; Chao Liu; Yuli Wu; Xidong Mu; Yi Liu (Fishes, 2025)
The zig-zag eel (Mastacembelus armatus) is a unique economic fish species in China and exhibits significant dimorphism of male and female phenotypes. Cultivating all-male seedlings can significantly improve production efficiency. To investigate sex differentiation and gonadal development in M. armatus, high-throughput sequencing technology was used to analyze the transcriptomes of male and female gonads at different developmental stages, both before and after sex differentiation. We identified key genes involved in sex differentiation, male-specific differentially expressed genes (DEGs), including dmrt1, amh, sox9, gsdf, and dmrt2b, and female-biased DEGs, including foxl2, rspo1, gdf9, bmp15, and wnt4. GO and KEGG enrichment analyses revealed that signaling pathways such as MAPK, Wnt, and TGF-β play significant roles in sex differentiation in M. armatus. The expression levels of 13 sex-related genes, including dmrt1, sox9, amh, foxl2, rspo1, and wnt4, were determined by RT–qPCR in addition to RNA sequencing. RT-qPCR validation results were consistent with the transcriptomic data, confirming the reliability of our findings. This research provides valuable insights into the mechanisms of sex differentiation in M. armatus and lays a foundation for developing all-male populations in aquaculture.

Co-culturing Limosilactobacillus fermentum and Pichia fermentans to ferment soybean protein hydrolysates: An effective flavor enhancement strategy - Chenchen Cao; Xueying Song; Yihan Mu; Weizheng Sun; Guowan Su (Innovative Food Science & Emerging Technologies, 2025)

Self-gelated flexible lignin-based ionohydrogels for efficient self-powered strain sensors - Jiahui Mu; Cuihuan Li; Deqiang Li; Xianliang Song; Sheng Chen; Feng Xu (Chemical Engineering Journal, 2025)

Cracking Behaviors of Rocks Subjected to the Dynamic Percussion of a Single PDC Cutter: A Finite-Discrete Element Study - Zhaowei Sun; Zhongwei Huang; Wenchao Zou; Xiaoguang Wu; Zongjie Mu; Xianwei Dai; Xianzhi Song; Wenhao He; Han Chen; Xinlong Li (Rock Mechanics and Rock Engineering, 2025)

An optimized non-landslide sampling method for Landslide susceptibility evaluation using machine learning models - Shuai Xu; Yingxu Song; Pin Lu; Guizhen Mu; Ke Yang; Shangxiao Wang (Natural Hazards, 2025)

Geosites Associated with Paleovolcanic Landscapes and Paleontology in Hoboksar Mongol Autonomous County, Xinjiang Uygur Autonomous Region, NW China - Hong-Xu Mu; Qing-Wei Song; Jun-Ting Qiu; Long-Xin Xu; Xin-Min Rui (Geoheritage, 2025)

Polypropylene microplastics triggered mouse kidney lipidome reprogramming combined with ROS stress as revealed by lipidomics and Raman biospectra - Mingying Liu; Miao Wang; Xinglin Sun; Ju Mu; Tingting Teng; Naifu Jin; Jiaxuan Song; Bei Li; Dayi Zhang (Chemosphere, 2025)

Unveiling the metabolic heterogeneity and formation mechanism in Chinese typical Daqu based on Qu-omics - Yu Mu; Shangjie Yao; Ying Huang; Zhiyu Zhu; Dong Li; Ya Song; Zehuan Liu; Chunlin Zhang; Shirui Yu (Food Research International, 2025)

Development of 68 SSR markers for Hemibagrus guttatus, a protected indigenous catfish in China - Yexin Yang; Yi Liu; Shandian Zhu; Bingyuan Xiong; Yuli Wu; Jiahuan Song; Chao Liu; Xidong Mu (Conservation Genetics Resources, 2025)

Exploring the synergistic effect of NaOH/NaClO absorbent in a novel wet FGD scrubber to control SOx/NOx emissions - Muhammad Rizwan; Muhammad Faryad Ali; Muhammad Asif Nawaz; Mu He; Yueqin Song; Peng Jiang; Saif Ullah; Malik M. Abdullah Hassan; Xiaolong Zhou (Environmental Monitoring and Assessment, 2025)

Diatom assemblages indicated ecological shifts over the past two centuries in Bosten Lake, northwest China: Natural and anthropogenic forcings - Muhammad Farqan; Lixiong Xiang; Lan Jiang; Wenjia Wang; Min Zheng; Xiaoyan Mu; Xin Liu; Xueqing Song; Zezhou Zhu; Ramamoorthy Ayyamperumal; Xiaozhong Huang (Quaternary International, 2025)

A comprehensive study on fermentation and aroma contributions of Torulaspora delbrueckii in diverse wine varieties: Insights from pure and co-fermentation studies - Yichao Cheng; Shijin Geng; Jin Zhang; Xixi Zhao; Jiao Jiang; Yanying Liang; Haibin Mu; Wenchao Li; Yi Qin; Yanlin Liu; Yuyang Song (Food Research International, 2025)

Enhanced chemiluminescence by carbon dots for rapid detection of bisphenol A and nitrite - Yujie Xiao; Xiaoqin Long; Xue Zhang; Junjie Mu; Qiuxiong Chen; Yuxian Mai; Ying Li; Hao Xue; Pengyang Song; Xian Yang; Hong Zheng (Food Chemistry, 2025)

Phase-separated anisotropic PVA hydrogel loaded with tetramethylpyrazine for spinal cord injury repair - Gang Liu; Shenglin Li; Bowen Deng; Luyao Huo; Huizhong Bai; Shengyuan Jiang; Yimin Zhou; Zhenzhen Pei; Ceren Kimna; Yi Zhao; Lin Xu; Jinyu Li; et al. (Chemical Engineering Journal, 2025)

The Characteristics of Sex Differentiation Based on Morphological Traits During the Early Development Stage of the Swimming Crab Portunus trituberculatus and Sex Prediction Model Comparison - Yanqing Peng; Junkai Lu; Ronghua Li; Chendong Xu; Shangbiao Zheng; Zhiming Ren; Chuan He; Changkao Mu; Weiwei Song; Chunlin Wang (Fishes, 2024)
To investigate the morphological traits of different sexes during the early development stage of the swimming crab Portunus trituberculatus, the genetic sex of 405 crablets from stages C I–V was determined using sex-linked molecular markers. The external appearance of each crab was observed, and the morphological traits, including carapace length (CL), full carapace width (FCW), abdomen width (AW), and abdomen length (AL), were measured to compare the differences between the sexes and to develop non-intrusive methods for sex identification. The genetic sex identification demonstrated that the female-to-male sex ratio at each stage did not deviate from 1:1. The gonopores of the females were first observed at stage C I using a scanning electron microscope; however, the shape difference in the abdominal flap between the sexes from stages C I to stage C V were not observed under a dissecting microscope. Correlation analysis showed that AW3 and AW4 were significantly correlated with sex at stage C V. Three methods were used to predict the sex of the crablets according to the morphological measurements; among them, the multinomial logistic regression (MLR) model performed better than the threshold method or the stepwise discriminant analysis, and the accuracy at stage C V increased to 90% when detailed abdominal parameters were included. These results indicate that it is feasible to predict sex during the early development stages of P. trituberculatus through morphometric and geometric parameters, which would be helpful for the creation of monosex populations of this species.

A multi-perspective exploration of the salinization mechanisms of groundwater in the Guanzhong Basin, China - Dawei Mu; Peiyue Li; Bernard De Baets; Dongfeng Li; Zhaoyu Li; Song He (Science of The Total Environment, 2024)

Annual emissions of N2O, NO, HONO, and NH3 from maize-wheat fields in the North China Plain - Yifei Song; Yuanyuan Zhang; Minhang Tan; Yining Hu; Pengfei Liu; Di Tian; Yujing Mu (Science of The Total Environment, 2024)

Effect of the quorum sensing signal molecule auto-inducer-2 on fermentation performance of Lactobacillus delbrueckii subsp. Bulgaricus DPUL-F36 - Xueqi Lu; Mengying Sun; Yuqing Chen; Dashuai He; Yanfeng Tuo; Guangqing Mu; Yinglong Song (Food Bioscience, 2024)

MoS2 coupled with ball milling co-modified sludge biochar to efficiently activate peroxymonosulfate for neonicotinoids degradation: Dominant roles of SO4•-, 1O2 and surface-bound radicals - Yifan Liu; Yongfei Ma; Zhikang Deng; Ping Li; Song Cui; Chenyu Zeng; Rui Mu; Yusheng Zhou; Xuebin Qi; Zulin Zhang (Environmental Research, 2024)

Enhancement and Preservation of Tufa Geosites in the Baishuitai Region, Yunnan Province, Southwest China - Hong-Xu Mu; Qing-Wei Song; Gui-Hua Wu; Long-Xin Xu (Geoheritage, 2024)

Paracoccus benzoatiresistens sp. nov., a benzoate resistance and selenite reduction bacterium isolated from wetland - Weidong Mu; Haoran Liu; Bai Guo; Kaiyue Wang; Jinhua Hu; Jianjun Song; Xiuyun Li; Shuzhen Wei; Aijv Liu; Hongliang Liu (Antonie van Leeuwenhoek, 2024)

Improvement of model simulation for summer PM2.5 and O3 through coupling with two new potential HONO sources in the North China Plain - Xiaoxi Zhao; Min Song; Xiujuan Zhao; Chaoyang Xue; Pengfei Liu; Can Ye; Xiaowei He; Yujing Mu; Bo Hu (Science of The Total Environment, 2024)

From flavor to function: A review of fermented fruit drinks, their microbial profiles and health benefits - Yu-Han Yuan; Dong-Dong Mu; Li Guo; Xue-Feng Wu; Xiang-Song Chen; Xing-Jiang Li (Food Research International, 2024)

Alternate wetting and drying maintains rice yield and reduces global warming potential: A global meta-analysis - Lin Li; Zheng Huang; Yixue Mu; Shaokun Song; Yicheng Zhang; Ye Tao; Lixiao Nie (Field Crops Research, 2024)

Sub-chronically exposing zebrafish to environmental levels of methomyl induces dysbiosis and dysfunction of the gut microbiota - Mingxiao Li; Xi Chen; Chao Song; Limin Fan; Liping Qiu; Dandan Li; Huimin Xu; Shunlong Meng; Xiyan Mu; Bin Xia; Jun Ling (Environmental Research, 2024)

Effect of fertilizer deep placement and nitrification inhibitor on N2O, NO, HONO, and NH3 emissions from a maize field in the North China Plain - Yifei Song; Minhang Tan; Yuanyuan Zhang; Xuran Li; Pengfei Liu; Yujing Mu (Atmospheric Environment, 2024)

Evaluation of the impacts of mining overburden bed separation grouting on the groundwater environment: a case study from Northern China - Tianhao Kou; Wenping Mu; Zexin Gao; Shuaixin Wen; Yubing Song (Bulletin of Engineering Geology and the Environment, 2024)

Evaluation of the collapse susceptibility of loess using machine learning - Qing-yi Mu; Tian-qi Song; Zhao Lu; Te Xiao; Li-min Zhang (Transportation Geotechnics, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Implications of ocean warming and acidification on heavy metals in surface seawater of the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Hazardous Materials, 2024)

Identification and application of a novel patulin degrading enzyme from Cyberlindnera fabianii - Chenyu Song; Wei Xu; Cuie Guang; Ting Xue; Wanmeng Mu (Food Research International, 2024)

A zero-dimensional perovskite with high-efficiency luminescence and transient response for advanced information encryption - Junheng Yuan; Tianchi Wang; Yu Zhang; Shuyi Yao; Lulu Han; Dedan Mu; Hao Song; Jiayi He; Feng Zhang; Xuhui Xu (Chemical Engineering Journal, 2024)

Ecological succession of eukaryotic community in epiphytic biofilms on Hydrilla verticillata in wetlands under norfloxacin stress - Xiaoying Mu; Songhe Zhang; Jianhui Lu; Ziqiu Zhang; Yingying Song (Process Safety and Environmental Protection, 2024)

Subnanometric Pt-Ga alloy clusters confined within Silicalite-1 zeolite for n-hexane dehydrogenation - Mu He; Guanyu Qie; Zhangfa Tong; Yueqin Song; Rizwan Muhammad; Xiaolong Zhou; Jin An Wang; Ping Lan (Fuel, 2024)

An edge feature-based external calibration of monocular camera and LiDAR using in-orbit data - Jiaqian Hu; Bin Song; Jinzhen Mu; Hanxue Zhao; Shuang Li (Advances in Space Research, 2024)

Functional Study on the BMP Signaling Pathway in the Molting of Scylla paramamosain - Botao Zhong; Huaihua Yu; Shengming Han; Weiwei Song; Zhiming Ren; Chunlin Wang; Changkao Mu (Fishes, 2024)
In this study, we added LDN-193189 2HCL to inhibit the BMP signaling pathway in Scylla paramamosain and then explored the function of this pathway in molting through the changes in the growth performance and molt-related gene expression. The study findings indicated that the expression of ACVR1, BMPRIB, and Smad1 in Scylla paramamosain was suppressed when the LDN-193189 2HCL concentration in the culture water was 2 µm/L. Subsequently, following a 30-day experiment, there was a significant reduction in the molting frequency, growth rate, and body size of the S. paramamosain larvae. An analysis of the BMP pathway gene expression during the molting phase revealed that the BMP2, BMPR2, and Smad1 genes displayed cyclic expression patterns, while ACVR1, BMP7, and BMPRIB maintained consistent expression levels throughout the molting cycle. Additionally, the expression levels of BMP2, BMPR2, and Smad1 in the inhibition group were significantly lower compared to those in the control group. Furthermore, the inhibition of the BMP pathway led to an increase in the expression of MIH during the intermolt period and a decrease in the expression of EcR during the premolt period. These findings demonstrate that the BMP signaling pathway affects the molting of Scylla paramamosain juvenile crabs by influencing the expression of the critical genes MIH and ECR during molting, offering valuable data for functional research on the BMP signaling pathway in crustaceans.

The superiority of hydrophilic polyurethane in comammox-dominant ammonia oxidation during low-strength wastewater treatment - Yunlong Li; Zimin Chai; Chao Song; Jin Chen; Ailu Gu; Guangli Mu; Ruxin Ge; Maosheng Zheng (Science of The Total Environment, 2024)

Repeated-dose toxicity and toxicokinetic study of isobutylparaben in rats subcutaneously treated for 13 weeks - Jung Dae Lee; Jin-Sook Bae; Hyang Yeon Kim; Si-Whan Song; Jong-Choon Kim; Byung-Mu Lee; Kyu-Bong Kim (Archives of Toxicology, 2024)

Synergistic developmental effects of zebrafish exposed to combined perfluorooctanoic acid and atrazine - Xiaoyu Zhao; Beinan Wang; Xiao Song; Linjuan He; Wei Zhang; Yongzhong Qian; Xiyan Mu; Jing Qiu (Chemosphere, 2024)

Environmental and human history in the hyper-arid eastern Tarim Basin (Lop Nur), northwest China: A critical review for sustaining the natural and cultural landscapes - Kangkang Li; Xiaoguang Qin; Bing Xu; Lei Zhang; Guijin Mu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Hongjuan Jia; Zhiqiang Yin; et al. (Quaternary International, 2024)

The greening of vegetation on the Loess Plateau has resulted in a northward shift of the vegetation greenness line - Xiaoyan Song; Peijun Xie; Wenyi Sun; Xingmin Mu; Peng Gao (Global and Planetary Change, 2024)

A continuous polymerase chain reaction 3D spiral microreactor capable of facile and on-demand fabrication - Qiushuang Yang; Wenchao Zhou; Huan Li; Jialing Huang; Zeyuan Song; Long Cheng; Yihui Wu; Deqiang Mu (Analytica Chimica Acta, 2024)

Identification and Characterization of microRNAs in Morphological Color Change of Polychromatic Midas Cichlids (Amphilophus citrinellus) - Guoqiang Wu; Xidong Mu; Yi Liu; Chao Liu; Xuejie Wang; Yexin Yang; Hongmei Song (Fishes, 2024)
As a representative genetic and economic trait, pigmentation has a strong impact on speciation and adaptation. However, information and reports on microRNAs (miRNAs) associated with pigmentation remain limited. The Midas cichlid fish, with three typical distinct stages of body color pattern, “black-gray-gold”, is an ideal model system for investigating pigmentation traits. In this study, miRNA libraries from scale tissues with the attached epidermis of Midas cichlids at three distinct stages of color transformation, black (B), transition (T), and gold (G), were sequenced using Illumina sequencing technology. In total, 53 (B vs. G), 88 (B vs. T), and 57 (T vs. G) miRNAs were differentially expressed between the respective groups. Target genes of the identified miRNAs were predicted, and the results showed that multiple target genes were related to pigmentation and pigment–cell differentiation. The miRNA–mRNA regulatory network suggests that miR-183-x and miR-133-x were predicted to be involved in regulating morphological color changes in Midas cichlids. The results advance our understanding of potential functions of miRNAs in skin pigment differentiation and early skin color fading of fishes.

Perfect cooperative pest control via nano-pesticide and natural predator: High predation selectivity and negligible toxicity toward predatory stinkbug - Shangyuan Wu; Qinhong Jiang; Zhilin Xia; Zhirong Sun; Qing Mu; Chunyang Huang; Fan Song; Meizhen Yin; Jie Shen; Hu Li; Shuo Yan (Chemosphere, 2024)

The positive effect of the enzyme inducer (MnSO4) on the formation of humic substance in rice straw composting by stimulating key microorganisms - Linying Mu; Runshi Dong; Jiaqi Wang; Jieyu Yue; Lina Pan; Caihong Song; Zimin Wei (Science of The Total Environment, 2024)

Utilizing Cs-TPA/Ce-KIT-6 solid-acid catalyst for enhanced biodiesel production from almond and amla oil feedstocks - Sivarasan Ganesan; Velu Manikandan; Mohammed F. Albeshr; Saurav Dixit; Kwang Soup Song; Huang-Mu Lo (Process Safety and Environmental Protection, 2024)

Global finite-time PLOS-OCCs guidance and adaptive integral sliding mode path following control for unmanned surface vehicles with ocean currents and input saturation - Zhiping He; Yunsheng Fan; Guofeng Wang; Dongdong Mu; BaoJian Song (Ocean Engineering, 2024)

Graphene oxide quantum dots (GOQDs) induce behavioral disorders via the disturbance of kynurenine pathway in zebrafish larvae - Shun Deng; Enming Zhang; Yunyang Zhao; Hao Guo; Lan Luo; Song Yi; Bingxin Zheng; Xiaoyuan Mu; Kezhu Yuan; Xuangen Deng; Haibo Rong; Yanbo Ma; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Employing Piper longum extract for eco-friendly fabrication of PtPd alloy nanoclusters: advancing electrolytic performance of formic acid and methanol oxidation - Thamaraiselvi Kanagaraj; Velu Manikandan; Sivarasan Ganesan; Mohammed F. Albeshr; R. Mythili; Kwang Soup Song; Huang-Mu Lo (Environmental Geochemistry and Health, 2024)

Enhancement of methane production from anaerobic digestion of Erigeron canadensis via O2-nanobubble water supplementation - Legeng Pei; Yingjin Song; Guanyi Chen; Lan Mu; Beibei Yan; Teng Zhou (Chemosphere, 2024)

Characteristics and sources of peroxyacetyl nitrate (PAN) in the rural North China Plain: Results from 1-year continuous observations - Xin Liu; Xiaowei He; Chenglong Zhang; Yifei Song; Shuyang Xie; Chengtang Liu; Pengfei Liu; Yuanyuan Zhang; Yujing Mu; Junfeng Liu (Journal of Environmental Sciences, 2024)

Adsorption of humic acid from different organic solid waste compost to phenanthrene, is fluorescence excitation or quenching? - Xinya Su; Ruju Zhang; Huan Cao; Daichen Mu; Liqin Wang; Caihong Song; Zimin Wei; Yue Zhao (Environmental Pollution, 2024)

Preparation of iron oxide-modified digestate biochar and effect on anaerobic digestion of kitchen waste - Yifan Wang; Lan Mu; Chen Chen; Fenglian Xu; Hao Peng; Yingjin Song; Guanyi Chen (Bioresource Technology, 2024)

Lactiplantibacillus plantarum DLPT4 Protects Against Cyclophosphamide-Induced Immunosuppression in Mice by Regulating Immune Response and Intestinal Flora - Yinglong Song; Mengying Sun; Fenglian Ma; Dongxue Xu; Guangqing Mu; Yang Jiao; Ping Yu; Yanfeng Tuo (Probiotics and Antimicrobial Proteins, 2024)

Comparative Transcriptome Analysis Reveals the Light Spectra Affect the Growth and Molting of Scylla paramamosain by Changing the Chitin Metabolism - Shujian Chen; Ce Shi; Yangfang Ye; Ronghua Li; Weiwei Song; Changbin Song; Changkao Mu; Zhiming Ren; Chunlin Wang (Marine Biotechnology, 2024)

Development and application of greenhouse light environment simulation technology based on light path tracing - Zhihui Mu; Yu Bo; Jihang Xu; Kai Song; Boda Dong; Jian Wang; Sheng Shu; Yu Wang; Shirong Guo (Computers and Electronics in Agriculture, 2024)

Multiple isotopes decipher the nitrogen cycle in the cascade reservoirs and downstream in the middle and lower Yellow River: Insight for reservoir drainage period - Jinglong Mu; Shuai Ding; Su Mei Liu; Guodong Song; Xiaoyan Ning; Xiaotong Zhang; Wenqi Xu; Hongmei Zhang (Science of The Total Environment, 2024)

Repeat dose and reproductive toxicity of thrombopoietin mimic peptide in Sprague-Dawley rats - Shidong Qiu; Yuji Liang; Xiaobo Wang; Xiue Li; Guoyue Wei; Peng Xiao; Suling Teng; Peilu Sun; Lei Song; Zenglin Zhao; Yanling Mu (Regulatory Toxicology and Pharmacology, 2024)

Provenance and sedimentary environment of REY-rich sediments from the Wharton Basin, Indian Ocean - Jia Li; Mu Huang; Miao Yu; Dongjie Bi; Xuefa Shi; Fengdeng Shi; Chengfei Hou; Zhaojun Song; Fangyu Shen; Aimei Zhu; Hui Zhang; Yonghua Wu; et al. (Journal of Asian Earth Sciences, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Nutrient dynamics in the Yellow River -a case study of different reservoir regulation operations - Jinglong Mu; Hongmei Zhang; Su Mei Liu; Nian Wu; Guodong Song; Shuai Ding; Xiaotong Zhang (Journal of Hydrology, 2024)

Enhancing envrionmental sustainability via interval optimization for low-carbon economic dispatch in renewable energy power systems: Leveraging the flexible cooperation of wind energy and carbon capture power plants - Jianzhao Song; Zhong Zhang; Yunye Mu; Xingyu Wang; Haipeng Chen; Qingze Pan; Yang Li (Journal of Cleaner Production, 2024)

Effect of heterogeneous fenton-like pretreatment on semi-permeable membrane-covered co-composting: Humification and microbial community succession - Yingjin Song; Yu Hou; Lan Mu; Guanyi Chen; Yamei Zeng; Beibei Yan (Bioresource Technology, 2024)

A statistical review on the optimal fingerprinting approach in climate change studies - Hanyue Chen; Song Xi Chen; Mu Mu (Climate Dynamics, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Establishment of CRISPR-Cas-based antiparasitic agents for the swimming crab parasite Mesanophrys sp. - Xiaopeng Wang; Yueyue Zhou; Yingchao Zhang; Xiaofen Song; Ce Shi; Yuanyuan Fu; Lei Liu; Changkao Mu; Fei Yin; Weiwei Song; Chunlin Wang (Aquaculture, 2024)

Comparative evaluation of soybean meal vs. extruded soybean meal as a replacer for fishmeal in diets of olive flounder (Paralichthys olivaceus): Effects on growth performance and muscle quality - Nannan Shen; Zhicheng Song; Cancan Xia; Hua Mu; Xiangning Chen; Hanliang Cheng; Jianhe Xu; Yongkai Sun; Chaoqing Wei; Lu Zhang (Aquaculture, 2024)

Effects of different visible light spectrums on phototaxis and bottom preference behavior of sea cucumber - Mu-Hsiang Wang; Yi-Jui Hsieh; Hsiu-Hua Chang; Yung-Song Wang (Aquaculture, 2024)

Optimal scheduling of zero-carbon integrated energy system considering long- and short-term energy storages, demand response, and uncertainty - Yujia Song; Hailin Mu; Nan Li; Hongye Wang; Xue Kong (Journal of Cleaner Production, 2024)

Coupling of submerged macrophytes and epiphytic biofilms reduced methane emissions from wetlands: Evidenced by an antibiotic inhibition experiment - Jianhui Lu; Xiaoying Mu; Songhe Zhang; Yingying Song; Yu Ma; Min Luo; Rufei Duan (Science of The Total Environment, 2023)

Significantly mitigating PM2.5 pollution level via reduction of NOx emission during wintertime - Shuang Fu; Pengfei Liu; Xiaowei He; Yifei Song; Junfeng Liu; Chenglong Zhang; Yujing Mu (Science of The Total Environment, 2023)

Geochronology and in-situ apatite geochemistry of late Paleoproterozoic A-type granites in the Jiao-Liao-Ji Belt, North China Craton: Implications for petrogenesis and tectonic evolution - Yi-Kang Quan; Mao-Song Mu; De-Bin Yang; Xiang-Yu Yan; An-Qi Wang; Le-Ran Hao; Feng Wang (Geochemistry, 2023)

Graphene-based biomimetic array film for simultaneous fog water harvesting and wind power generation - Tsung Han Huang; Mu-Jie Shih; Yi-Yun Chen; Hannah Faye M. Austria; Owen Setiawan; Chunrui Wu; Xiaolong Lu; Lin Zhang; Wei-Song Hung (Chemical Engineering Journal, 2023)

Bioavailability-based risk assessment of various heavy metals via multi-exposure routes for children and teenagers in Beijing, China - Zhongwen Du; Zuguang Tian; Yelan Yin; Junxiao Wei; Yue Mu; Jianjun Cai; Zefeng Song; Kuang Cen (Environmental Science and Pollution Research, 2023)

Passenger spatiotemporal distribution prediction in airport terminals based on insect intelligent building architecture and its contribution to fresh air energy saving - Zhiwei Li; Jili Zhang; Song Mu (Sustainable Cities and Society, 2023)

PANI grafted onto waste poros polyurethane for co-adsorption of multiple pollutants in industrial wastewater - Ning Wang; Yirui Guo; Yi Song; Wei Yan; Xuesong Gong; Yunfeng Li; Rui hua Mu; Yonghong Liu; Luohong Zhang (Journal of Water Process Engineering, 2023)

Fermented milk by Lactobacillus delbrueckii, Lacticaseibacillus paracasei, and Kluyveromyces marxianus shows special physicochemical and aroma formation during the storage - Mengying Sun; Jiang Yu; Yinglong Song; Xinling Li; Guangqing Mu; Yanfeng Tuo (Food Bioscience, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

Bioaccumulation and elimination, acute toxicity analysis and risk assessment of diflubenzuron in common carp (Cyprinus carpio) - Lu Qiao; Lu Chen; Zhen Yang; Jinhua Xu; Jinlong Song; Xingyang Li; Huiwu Sun; Yingchun Mu (Chemosphere, 2023)

Hierarchical extraction of cropland boundaries using Sentinel-2 time-series data in fragmented agricultural landscapes - Wenyao Song; Chen Wang; Taifeng Dong; Zhaohai Wang; Chengxin Wang; Xiaoda Mu; Huanxue Zhang (Computers and Electronics in Agriculture, 2023)

Numerical study on the VIVs of two side-by-side elastically coupled cylinders under different Re and natural frequencies - Guangjun Liu; Zhiyou Song; Wanhai Xu; Mu Sha (Ocean Engineering, 2023)

Multi-omics reveals 2-bromo-4,6-dinitroaniline (BDNA)-induced hepatotoxicity and the role of the gut-liver axis in rats - Fuchang Deng; Guangqiu Qin; Yuanyuan Chen; Xu Zhang; Mu Zhu; Min Hou; Qiao Yao; Wen Gu; Chao Wang; Hui Yang; Xudong Jia; Chongming Wu; et al. (Journal of Hazardous Materials, 2023)

Isovitexin prevents DSS-induced colitis through inhibiting inflammation and preserving intestinal barrier integrity through activating AhR - Jianfeng Mu; Jiaxing Song; Rong Li; Tianyi Xue; Dongxu Wang; Jinhai Yu (Chemico-Biological Interactions, 2023)

Efficient denitrification by a salt-tolerant aerobic compound bacteria agent AHM M3: optimizing composition and reduction conditions - H. Ma; Y. Liu; X. Mu; J. Song; X. Su; Y. Wu; R. Han (International Journal of Environmental Science and Technology, 2023)

Metabolomic analysis of fermented milk with Lactobacillus delbrueckii subsp. bulgaricus, Lacticaseibacillus paracasei cocultured with Kluyveromyces marxianus during storage - Mengying Sun; Jiang Yu; Yinglong Song; Xinling Li; Guangqing Mu; Yanfeng Tuo (Food Bioscience, 2023)

Identification for the species of aquatic higher plants in the Taihu Lake basin based on hyperspectral remote sensing - Shichen Mu; Kai You; Ting Song; Yajie Li; Lihong Wang; Junzhe Shi (Environmental Monitoring and Assessment, 2023)

Temperature and light dependency of isoprene and monoterpene emissions from tropical and subtropical trees: Field observations in south China - Jianqiang Zeng; Yanli Zhang; Zhaobin Mu; Weihua Pang; Huina Zhang; Zhenfeng Wu; Wei Song; Xinming Wang (Applied Geochemistry, 2023)

Defect modes and localisation of quasi-Lamb waves along a sidewall of corrugated aluminium plates - Qiao-Mu Zhang; Ya-Xian Fan; Le Song; Huan Liu; Yu Su; Zhi-Yong Tao (Wave Motion, 2023)

Aging of pollution air parcels acts as the dominant source for nocturnal HONO - Wenjin Zhang; Yangang Ren; Chenglong Zhang; Pengfei Liu; Chaoyang Xue; Can Ye; Chengtang Liu; Jinhe Wang; Yuanyuan Zhang; Junfeng Liu; Yifei Song; Yinchang Feng; et al. (Science of The Total Environment, 2023)

Fault detection and calibration for building energy system using Bayesian inference and sparse autoencoder: A case study in photovoltaic thermal heat pump system - Peng Wang; Congwei Li; Ruobing Liang; Sungmin Yoon; Song Mu; Yuchuan Liu (Energy and Buildings, 2023)

Comparative transcriptome analysis reveals the growth and development in larval stages of the swimming crab Portunus trituberculatus - Jiameng Chen; Xiayue Chen; Changkao Mu; Chunlin Wang; Yangfang Ye; Ronghua Li; Weiwei Song; Ce Shi; Lei Liu; Huan Wang (Frontiers in Marine Science, 2023)
Portunus trituberculatus , an economically important marine crab that was widely distributed along the coast of China, has been in short supply of high-quality crab seedlings in recent years. The larval development of P. trituberculatus is regulated by numerous biological processes at different biological levels, particularly regarding gene expression during the larval development process. Understanding the changes in these critical genes can help further regulate these biological processes to increase crab seedlings’ survival and improve crab quality. In this study, the molecular mechanisms of morphological and physiological changes in larval stages of P. trituberculatus were investigated using DNA microarrays. A total of 109,533 unigenes were obtained, of which 16 genes were differentially expressed during the whole development stages with evident timeliness. The enrichment analysis and comparison of differentially expressed genes (DEGs) showed three types of physiological activities, chitin development, energy metabolism, and neuroendocrine development. The physiological activities were evident in the early development of P. trituberculatus , especially at the Z4-M stage, which is crucial for the growth and development of crab larvae. These DEGs, cuticle proteins, retinol dehydrogenase (RDHs), Juvenile Hormone Epoxide Hydrolase (JHEH), and other vital genes were differentially expressed at the Z4-M stage. Moreover, the insulin-like androgenic gland (IAG), which was reported to be associated with sex differentiation, was highly expressed in the megalopa stage, indicating that the gender differentiation divide may occur at the beginning of this stage. Overall, this research provides a theoretical basis for the development of the swimming crab larvae, which could contribute to the artificial growing seedlings technology of P. trituberculatus .

Comprehensive analysis and identification of the circ_0084615/miR-451a/MEF2D axis in benzo(a)pyrene exposed tumor cells in hepato-carcinogenesis - Wei Mu; Pengfei Gu; Weiwei Song; Tengfei Zhu; Wenbo Wang; Yanfeng Zhou (Food and Chemical Toxicology, 2023)

Mitochondrial Lipid Peroxidation and Microsomal Drug-metabolizing Enzyme Activity of Rat Hepatotoxicity under Heavy Metals from Slag Waste Exposure - Haishuo Mu; Wangjun Wan; Jingwu Song; Rong Kuang; Tongle Deng (Cell Biochemistry and Biophysics, 2023)

Effects of solar radiation and fine roots on suction of Amorpha fruticose-vegetated soil - Han-qing Guo; Xiao-qing Chen; Dong-ri Song; Qing-yi Mu; Hamed Sadeghi; Hao Jiang; Ming Lv (Journal of Mountain Science, 2023)

Wind Speed Prediction Based on VMD-BLS and Error Compensation - Xuguo Jiao; Daoyuan Zhang; Dongran Song; Dongdong Mu; Yanbing Tian; Haotian Wu (Journal of Marine Science and Engineering, 2023)
As one of the fastest-growing new energy sources, wind power technology has attracted widespread attention from all over the world. In order to improve the quality of wind power generation, wind speed prediction is an indispensable task. In this paper, an error correction-based Variational Mode Decomposition and Broad Learning System (VMD-BLS) hybrid model is proposed for wind speed prediction. First, the wind speed is decomposed into multiple components by the VMD algorithm, and then an ARMA model is established for each component to find the optimal number of sequence divisions. Second, the BLS model is used to predict each component, and the prediction results are summed to obtain the wind speed forecast value. However, in some traditional methods, there is always time lag, which will reduce the forecast accuracy. To deal with this, a novel error correction technique is developed by utilizing BLS. Through verification experiment with actual data, it proves that the proposed method can reduce the phenomenon of prediction lag, and can achieve higher prediction accuracy than traditional approaches, which shows our method’s effectiveness in practice.

Dynamic Distribution of Mesanophrys sp. and Tissue Enzyme Activities in Experimentally Infected Mud Crab Scylla paramamosain - Kexin Zhang; Weiren Zhang; Ronghua Li; Junkai Lu; Qingwei Chen; Haojie Hu; Fei Yin; Changkao Mu; Weiwei Song; Chunlin Wang (Fishes, 2023)
Mesanophrys sp. is reported to be highly pathogenic to marine crustaceans. This study presents the first report of Mesanophrys sp. infection in the mud crab (Scylla paramamosain). In this study, we first recorded the survival rates of an experimentally infected group and a control group; the cumulative survival rate in the infected group was significantly lower compared to the control group after 72 h (73.20% vs. 94.19%), while the highest mortality of S. paramamosain occurred within the first 24 h post-infection. Then, we investigated the dynamic distribution and tissue tropism of the Mesanophrys sp. in the infected S. paramamosain by a quantitative real-time polymerase chain reaction (qPCR). The result showed that a significant increase in the number of Mesanophrys sp. could be detected in all tested tissues (obtained from the eyestalks, gills, heart, nerves, muscles and hepatopancreas) at 3 h post-infection. The numbers of Mesanophrys sp. in the gill, eyestalk and nerve tissues were relatively higher than in the other tissues. The gill tissue showed the highest numbers from 6 to 48 h. Histopathological observation found a severe collapse in the filament structure, which indicated tissue-specific pathogen infection. Furthermore, the antioxidant enzyme activity of superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) in three representative tissues (gill, muscle and hepatopancreas) were compared between the infected and control groups, and a significant increase in enzyme activity was observed in all three tested tissues in the infected group, indicating a relatively strong innate immune defense reaction that could have been induced by Mesanophrys sp. infection. These results will be helpful to Mesanophrys sp. pathogenicity-related research and the control of this pathogen in S. Paramamosain in the future.

Review of ground and aerial methods for vegetation cover fraction (fCover) and related quantities estimation: definitions, advances, challenges, and future perspectives - Linyuan Li; Xihan Mu; Hailan Jiang; Francesco Chianucci; Ronghai Hu; Wanjuan Song; Jianbo Qi; Shouyang Liu; Jiaxin Zhou; Ling Chen; Huaguo Huang; Guangjian Yan (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Light Intensity and Photoperiod Interaction Affects the Survival, Development, Molting and Apoptosis-Related Genes of Swimming Crab Portunus trituberculatus Larvae - Yun Zhao; Juan Dou; Hanying Xu; Zhen Ma; Yangfang Ye; Changkao Mu; Weiwei Song; Zhiming Ren; Chunlin Wang; Ce Shi (Fishes, 2023)
A 19-day experiment was conducted to investigate the optimal light intensity and photoperiod combination for larval swimming crabs Portunus trituberculatus in terms of survival, development, and apoptosis-related gene expression. Two photoperiods, i.e., 12 and 18 h photophases, and three light intensities, i.e., 126.08, 173.17, and 191.53 μmol m−2 s−1, were used in the study. The results showed that the cumulative survival rate (CSR) of larvae decreased with the increasing light intensity, and the adverse effect of high light intensity was only observed in long photophase groups. On the contrary, a long photophase and low light intensity elevated the CSR from zoea III to juvenile crabs. A long photophase also accelerated the development of zoea III larvae and upregulated the molting-related (ecr and rxr) and apoptosis-related (jnk, p53, and bcl-2) gene expressions. Taken together, the present study suggested that the light intensity and the photoperiod had a combined effect on P. trituberculatus larvae. The optimal light intensity and photoperiod for P. trituberculatus larvae were 126.08 μmol m−2 s−1 and an 18 h photophase, respectively.

Influence of Lonicera japonica and Radix Puerariae crude extracts on the growth performance, antioxidant capacity, and immunological functions of finishing pigs - Zhonghao Liu; Jun Yan; Ning Li; Zi Zheng; Chunhua Zhang; Zhengqun Liu; Chunling Song; Shuqin Mu (Livestock Science, 2023)

Basal Forebrain Cholinergic Innervation Induces Depression-Like Behaviors Through Ventral Subiculum Hyperactivation - Nana Yu; Huina Song; Guangpin Chu; Xu Zhan; Bo Liu; Yangling Mu; Jian-Zhi Wang; Yisheng Lu (Neuroscience Bulletin, 2023)
Malfunction of the ventral subiculum (vSub), the main subregion controlling the output connections from the hippocampus, is associated with major depressive disorder (MDD). Although the vSub receives cholinergic innervation from the medial septum and diagonal band of Broca (MSDB), whether and how the MSDB-to-vSub cholinergic circuit is involved in MDD is elusive. Here, we found that chronic unpredictable mild stress (CUMS) induced depression-like behaviors with hyperactivation of vSub neurons, measured by c-fos staining and whole-cell patch-clamp recording. By retrograde and anterograde tracing, we confirmed the dense MSDB cholinergic innervation of the vSub. In addition, transient restraint stress in CUMS increased the level of ACh in the vSub. Furthermore, chemogenetic stimulation of this MSDB-vSub innervation in ChAT - Cre mice induced hyperactivation of vSub pyramidal neurons along with depression-like behaviors; and local infusion of atropine, a muscarinic receptor antagonist, into the vSub attenuated the depression-like behaviors induced by chemogenetic stimulation of this pathway and CUMS. Together, these findings suggest that activating the MSDB-vSub cholinergic pathway induces hyperactivation of vSub pyramidal neurons and depression-like behaviors, revealing a novel circuit underlying vSub pyramidal neuronal hyperactivation and its associated depression.

Did Species and Functional Diversities of Sandy Intertidal Marine Nematodes Reveal Similar Response to Environmental Changes? - Huili Song; Fanghong Mu; Yan Sun; Er Hua (Journal of Ocean University of China, 2023)

Evaluation of the ventilation and pollutant exposure risk level inside 3D street canyon with void deck under different wind directions - Chung Hyok Sin; Kwang Song Jon; Gyong Ho Un; Yong Il Thae; Hun Kim; Jun Tokgo; Hyon Mu Ri (Environmental Science and Pollution Research, 2023)

Effect of photoperiod on growth, survival, and lipid metabolism of mud crab Scylla paramamosain juveniles - Shujian Chen; Jiahao Liu; Ce Shi; Herve Migaud; Yangfang Ye; Changbin Song; Changkao Mu; Zhiming Ren; Chunlin Wang (Aquaculture, 2023)

Simultaneous determination of the residues of anesthetics and sedatives in fish using LC-QLIT-MS/MS combined with DSPE - Qin Huang; Hua Zhou; Xianglun Wu; Chenli Song; Jiangang Zheng; Meikang Lei; Pengqian Mu; Pinggu Wu (Food Chemistry, 2023)

Coupling coordination relationships between air pollutant concentrations and emissions in China - Qian Wu; Song Hong; Lu Yang; Hang Mu; Chaoqing Huang; Xiaoxiao Niu; Yanmei Zhong; Jiahui Yi; Chao He (Atmospheric Pollution Research, 2023)

Multi-objective combinatorial optimization analysis of the recycling of retired new energy electric vehicle power batteries in a sustainable dynamic reverse logistics network - Nengye Mu; Yuanshun Wang; Zhen-Song Chen; Peiyuan Xin; Muhammet Deveci; Witold Pedrycz (Environmental Science and Pollution Research, 2023)

Atmospheric ammonia in the rural North China Plain during wintertime: Variations, sources, and implications for HONO heterogeneous formation - Pengfei Liu; Hui Chen; Yifei Song; Chaoyang Xue; Can Ye; Xiaoxi Zhao; Chenglong Zhang; Junfeng Liu; Yujing Mu (Science of The Total Environment, 2023)

Recent advancements in strategies to improve anaerobic digestion of perennial energy grasses for enhanced methane production - Yingjin Song; Legeng Pei; Guanyi Chen; Lan Mu; Beibei Yan; Hongji Li; Teng Zhou (Science of The Total Environment, 2023)

Core-shell structural vanadium Oxide/Polypyrrole anode for aqueous Ammonium-Ion batteries - Xinjian Mu; Yu Song; Zengming Qin; Jianming Meng; Zhihui Wang; Xiao-Xia Liu (Chemical Engineering Journal, 2023)

Indole acetylated high-amylose maize starch: Synthesis, characterization and application for amelioration of colitis - Yingying Song; Xinyan Qu; Mei Guo; Qiongzheng Hu; Yan Mu; Na Hao; Yunbo Wei; Quanbo Wang; Charles R. Mackay (Carbohydrate Polymers, 2023)

New (4 → 2)-abeo-clerodane diterpenoids from the Polyalthia laui and their chemotaxonomic significance - Zhang-Xin Yu; Xin-Ming Song; Mu-Yuan Li; Man-Man Zhang; Li-Zhu Huang; Xiao-Bao Li (Biochemical Systematics and Ecology, 2023)

Comparison of short-term toxicity of 14 common phycotoxins (alone and in combination) to the survival of brine shrimp Artemia salina - Yuting Zhang; Shanshan Song; Bin Zhang; Yang Zhang; Miao Tian; Ziyi Wu; Huorong Chen; Guangmao Ding; Renyan Liu; Jingli Mu (Acta Oceanologica Sinica, 2023)

Ozone exposure and health risks of different age structures in major urban agglomerations in People’s Republic of China from 2013 to 2018 - Lu Yang; Song Hong; Hang Mu; Jingwei Zhou; Chao He; Qian Wu; Xi Gong (Environmental Science and Pollution Research, 2023)

Biomass-derived polyphosphazene toward simultaneously enhancing the flame retardancy and mechanical properties of epoxy resins - Yuling Xiao; Xiaowei Mu; Siqi Chen; Guangyong Jiang; Zhoumei Xu; Chao Ma; Lei Song; Yuan Hu (Chemosphere, 2023)

A critical review of sulfate aerosol formation mechanisms during winter polluted periods - Can Ye; Keding Lu; Huan Song; Yujing Mu; Jianmin Chen; Yuanhang Zhang (Journal of Environmental Sciences, 2023)

Performance and mechanisms for tetrabromobisphenol A efficient degradation in a novel homogeneous advanced treatment based on S2O42− activated by Fe3+ - Wei Song; Mu Li; Sen Xu; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Wenhui Qiu; Zhihong Wang; Qi Song; Kalpana Bhatt; Caixia Fu (Environmental Pollution, 2023)

Single atom Co-anchored nitrogen‑doped graphene for peroxymonosulfate activation with high selectivity of singlet oxygen generation - Han-Qing Zhao; Jun-Sheng Song; Peili Lu; Yang Mu (Chemical Engineering Journal, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Study on the deactivation mechanism of HZSM-5 in the process of catalytic cracking of n-hexane - Mu He; Muhammad-Faryad Ali; Yue-Qin Song; Xiao-Long Zhou; Jin An Wang; Xin-Yao Nie; Zheng Wang (Chemical Engineering Journal, 2023)

Co-composting of cattle manure and wheat straw covered with a semipermeable membrane: organic matter humification and bacterial community succession - Yingjin Song; Ruiyi Li; Yuxin Wang; Yu Hou; Guanyi Chen; Beibei Yan; Zhanjun Cheng; Lan Mu (Environmental Science and Pollution Research, 2022)

Recognizing and managing construction land reduction barriers for sustainable land use in China - Jia-He Zhou; Yu-Ming Zhu; Lei He; Hao-Jing Song; Bing-Xu Mu; Fen Lyu (Environment, Development and Sustainability, 2022)

A novel victorivirus isolated from the tobacco spot blight fungus Stagonosporopsis cucurbitacearum in China - Mengmeng Yang; Guiyao Wang; Wenjun Mu; Jianhua Guo; Jiaqin Xi; Liwei Hu; Kexin Liang; Qiang Xu; Zongyu Hu; Jizhen Song (Archives of Virology, 2022)

Light spectrum impacts on development respiratory metabolism and antioxidant capacity of larval swimming crab Portunus trituberculatus - Feifei Zhang; Shuai Zhang; Zhiming Ren; Changbin Song; Yangfang Ye; Changkao Mu; Chunlin Wang; Ce Shi (Frontiers in Marine Science, 2022)
The effects of the spectrum on the development, respiratory metabolism, and antioxidant capacity of the larval swimming crab Portunus trituberculatus were studied. Seven light spectra, i.e ., purple (400 nm), blue (425 nm), cyan (510 nm), green (525 nm), yellow (598 nm), red (638 nm), and white (full spectrum), were estimated. The larvae had the optimum survival rate and development under cyan light. On the contrary, larvae in red and yellow lights had poor growth performance. The oxygen consumption rate (OCR) dropped while the ammonia excretion rate (AER) rose as the larvae developed. Early larvae’s oxygen-nitrogen ratio (O: N) fell when exposed to red light, suggesting more protein was utilized in the respiratory process. Regarding the antioxidant system, crab had the lowest malondialdehyde (MDA) under green, cyan and yellow light, and the highest total antioxidant capacity (T-AOC) in cyan light. Taken together, the current results suggest that cyan was the optimum spectrum for the development of P. trituberculatus larvae.

Pollution heaven or pollution halo? Assessing the role of heterogeneous environmental regulation in the impact of foreign direct investment on green economic efficiency - Hui Zheng; Li Zhang; Weiling Song; Hairong Mu (Environmental Science and Pollution Research, 2022)

Efficient degradation of semi-coking wastewater in three-dimensional electro-Fenton by CuFe2O4 heterocatalyst - Wen-wen Gao; Ting Su; Wei Zhao; Zhi-fang Zhang; Miao Mu; Yong-hui Song; Xue-xue Zhang; Xin-yu Liu (Environmental Science and Pollution Research, 2022)

Protective Effects of Sepia Ink Melanin on Hepatic Tissue in Streptozotocin-Induced Diabetic Mice - Xiaopeng Wang; Meng Han; Hui Dong; Yun Zhao; Weiwei Song; Chunlin Wang; Changkao Mu; Ronghua Li (Journal of Ocean University of China, 2022)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

The differential impact of air pollutants on acute urticaria and chronic urticaria: a time series analysis - Jiawei Li; Guoqiang Song; Zhenzhen Mu; Xiaoou Lan; Fan Yang; Lin Li; Xiuping Han (Environmental Science and Pollution Research, 2022)

Xinfangfangia pollutisoli sp. nov., Isolated from Clopyralid-Contaminated Soil - Yang Mu; Jia-Yi Peng; Hui-Ping Wang; Yue Song; Hong-Mei Wang; Qing Chen; Kai Chen (Current Microbiology, 2022)

A 215-bp indel at intron I of BoFLC2 affects flowering time in Brassica oleracea var. capitata during vernalization - Qinfei Li; Ao Peng; Jiaqin Yang; Sidi Zheng; Zhangping Li; Yinhui Mu; Lei Chen; Jun Si; Xuesong Ren; Hongyuan Song (Theoretical and Applied Genetics, 2022)

Physiological and Molecular Analyses of Low-Salinity Stress Response in the Cuttlefish (Sepia pharaonis) Juveniles - Hongwei Xin; Kunlan Wu; Yimeng Yuan; Yun Zhao; Weiwei Song; Chunlin Wang; Changkao Mu; Ronghua Li (Journal of Ocean University of China, 2022)

Photoperiod affects the survival rate but not the development of larval swimming crab Portunus trituberculatus - Hanying Xu; Juan Dou; Qingyang Wu; Yangfang Ye; Chunlin Wang; Changbin Song; Changkao Mu; Zhiming Ren; Ce Shi (Aquaculture International, 2022)

Wood decay fungi: an analysis of worldwide research - Tong Li; Lizhen Cui; Xiufang Song; Xiaoyong Cui; Yulian Wei; Li Tang; Yanhong Mu; Zhihong Xu (Journal of Soils and Sediments, 2022)
Purpose Wood decay fungi are the only forms of life capable of degrading wood to its initial constituents, greatly contributing to the soil ecosystem. This study summarizes the current research status and development characteristics of global wood decay fungi research, in order to better understand their role in soils. Methods A bibliometric analysis was applied to the literature from 1913 to 2020, based on data from the Web of Science (WOS) Core Collection. For this, various bibliometric analysis methods, R (Biblioshiny package), and VOSviewer were applied. Results A total of 8089 documents in this field were identified in the WOS Core Collection. The annual number of publications tended to increase, with exponential growth after 2008. Researchers in this field were mainly concentrated in North Europe, the USA, and China. Biotechnology, applied microbiology, environmental sciences, and microbiology were the most popular WOS categories. Bioresource Technology and Applied Environmental Microbiology were the top two journals with the most citations. The top three authors with the most published papers were Dai YC, Martinez AT, and Cui BK. Co-occurrence analysis of author keywords identified six clusters, mainly divided into three categories: the classification and diversity, the degradation mechanisms, and the ecological functions of wood decay fungi. Clustering results further showed that the lignin degradation process and the application of wood decay fungi in industrial production and soil contamination remediation are current research hotspots. Conclusions We present a comprehensive and systematic overview of research related to wood decay fungi and provide a deep perspective to understand the associated research progress. This is important for facilitating the development of a profound understanding of the contribution of wood decay fungi to soil systems and the degradation of soil contaminants.

Investigation of the Light Intensity Effect on Growth, Molting, Hemolymph Lipid, and Antioxidant Capacity of Juvenile Swimming Crab Portunus trituberculatus - Hanying Xu; Juan Dou; Qingyang Wu; Yangfang Ye; Changbin Song; Changkao Mu; Chunlin Wang; Zhiming Ren; Ce Shi (Frontiers in Marine Science, 2022)
An eight-week experiment was conducted to evaluate the effects of eight light intensities (0, 0.83, 1.61, 8.17, 15.89, 31.38, 63.69, and 124.31 μmol m -2 s -1 ) on the survival, growth, antioxidant, molting-related and apoptosis-related gene expression of juvenile swimming crab Portunus trituberculatus . The results showed that the survival rate of crabs was the highest under the light intensities of 8.17 and 15.89 μmol m -2 s -1 . Under this light intensity, the crabs had the lowest hemolymph glucose (GLU) but the highest triglyceride (TG) content. The crabs in these treatments also had the highest total antioxidant capacity (T-AOC), superoxide dismutase (SOD), catalase (CAT) activities, and the lowest malondialdehyde (MDA) content. The growth performance (including weight gain and specific growth rate) and molting frequency of crabs increased with increasing light intensity. The improved growth performance and molting of 8.17 and 15.89 μmol m -2 s -1 groups were also accompanied by up-regulated of the retinoid-X receptor ( rxr ), ecdysone receptor ( ecr ), nuclear receptor E75 ( e75 ) gene expression, and down-regulated molt-inhibiting hormone ( mih ) gene expression. In addition, suboptimal light intensity (0, 0.83, 63.69, and 124.31 μmol m -2 s -1 ) significantly up-regulated the expression of apoptosis-related genes including c-Jun N-terminal kinase ( jnk ), tumor suppressor p53 ( p53 ), and B-cell lymphoma-2 ( bcl-2 ). Taken together, the suitable light intensity for the juvenile P. trituberculatus was estimated to be 9.96 μmol m -2 s -1 .

IgE Reactivity of Potential Allergens from the Swimming Crab Portunus trituberculatus and the Research of ELISA Reagent for Detecting Crab Food Anaphylaxis - Xueni Qiu; Qiongyan Zhou; Xiaoxia Zhu; Wei Lin; Changkao Mu; Ronghua Li; Yangfang Ye; Weiwei Song; Ce Shi; Lei Liu; Huan Wang; Chunlin Wang; et al. (Journal of Ocean University of China, 2022)

Light Spectrum Impacts on Growth, Molting, and Oxidative Stress Response of the Mud Crab Scylla paramamosain - Shujian Chen; Ce Shi; Herve Migaud; Changbin Song; Changkao Mu; Yangfang Ye; Chunlin Wang; Zhiming Ren (Frontiers in Marine Science, 2022)
An 8 weeks trial was performed to test the effects of light spectra [full-spectrum, violet (405 nm), blue (470 nm), cyan (500 nm), green (525 nm), yellow (570 nm), and red (625 nm)] on growth performance, molting, antioxidant capacity, stress response and expression of molting, and apoptosis-related genes in Scylla paramamosain . Results showed that spectrum had a significant effect on S. paramamosain physiology. Compared to blue light, crabs exposed to violet light had a significantly lower survival rate (79.5 ± 3.6% vs. 94.9 ± 3.6%), weight gain (49.2 ± 5.4 vs. 67.6 ± 6.7), molt frequency (4.2 ± 0.2 vs. 4.5 ± 0.1), and extended intermolt intervals between instar 1 and 2 stages (C1–C2) (6.3 ± 0.3 vs. 5.0 ± 0.1 days). Expression of the molt-inhibiting hormone ( mih ) gene was upregulated in crabs reared under violet light. According to the regression analysis, maximum SGR would be at 449.97 nm. Crabs exposed to blue light also had lower melatonin levels than under full-spectrum and lower cortisol levels than violet and yellow groups. Regarding oxidative stress, crabs in full-spectrum had lower H 2 O 2 and MDA contents, however, no significant difference was found in total antioxidant capacity (T-AOC), superoxide dismutase (SOD), and catalase (CAT) in hepatopancreas from crabs under different spectra. Gene expression of hsp40 , hsp70 , hsp90 were down-regulated in crabs exposed to the full-spectrum light group. Regarding apoptosis-related genes, bcl-2 gene expression in crabs under cyan and the cox IV and caspase 3 in green were upregulated, suggesting cyan light may inhibit, while green light may promote apoptosis. Taken together, these results suggest that blue or cyan light would promote growth performance, while full-spectrum light could reduce stress response in S. paramamosain .

First report of Pseudocercospora coprosmae causing leaf spot on Scaevola taccada in China - Min Li; Zhaoyin Gao; Xiqiang Song; Qing Chen; Deqiang Gong; Junxia Mu; Meijiao Hu (Journal of Plant Pathology, 2022)

Effect of Long-Term Low-Salinity Culture on the Survival, Growth, and Nutrient Composition of Mud Crab Scylla paramamosain - Zilu Ji; Ronghua Li; Chunlin Wang; Zhouyi Zhang; Weijia Zhang; Changkao Mu; Weiwei Song (Journal of Ocean University of China, 2022)

Classification of electrocardiogram signals with waveform morphological analysis and support vector machines - Hongqiang Li; Zhixuan An; Shasha Zuo; Wei Zhu; Lu Cao; Yuxin Mu; Wenchao Song; Quanhua Mao; Zhen Zhang; Enbang Li; Juan Daniel Prades García (Medical & Biological Engineering & Computing, 2022)

Cytotoxic benzopyranone and xanthone derivatives from a coral symbiotic fungus Cladosporium halotolerans GXIMD 02502 - Chao-Nan Wang; Hu-Mu Lu; Cheng-Hai Gao; Lang Guo; Zhen-Yu Zhan; Jun-Jian Wang; Yong-Hong Liu; Song-Tao Xiang; Jian Wang; Xiao-Wei Luo (Natural Product Research, 2021)

Exploring the Occurrence Characteristics of Microplastics in Typical Maize Farmland Soils With Long-Term Plastic Film Mulching in Northern China - Jiajia Zhang; Guoyuan Zou; Xuexia Wang; Wencheng Ding; Li Xu; Baoyin Liu; Yunsen Mu; Xuran Zhu; Lianjie Song; Yanhua Chen (Frontiers in Marine Science, 2021)
Microplastics pollution has been threatening the global environmental security, in which agricultural activities are considered as a main source of microplastics occurrence in soils. However, little is known about the occurrence characteristics of microplastics in agricultural soils with long-term plastic film mulching. Therefore, the abundance, distribution, and composition of microplastics were investigated by analyzing 225 soil samples collected from typical maize ( Zea mays L.) planting zones with and without long-term (>20 years) plastic film mulching in northern China. Microplastics abundance in mulched soils (754 ± 477 items kg –1 ) was significantly higher than that in non-mulched soils (376 ± 149 items kg –1 ), which indicated that plastic film mulching contributed half of microplastics in soils. Moreover, microplastics abundance was significantly positively related to the length of time with film mulching applied. The percentage of microplastics <0.5 mm in mulched soils (50.9%) was significantly lower than that in non-mulched soils (62.2%). Microplastics abundance and size in mulched and non-mulched soils decreased with increased soil depth. Most microplastics were fragments of polypropylene, films of polyethylene, and fibers of polyester. The proportion of films in mulched soils was significantly higher than in non-mulched soils, whereas that of fibers was significantly higher in non-mulched soils. This study confirmed that long-term plastic film mulching increases microplastics pollution in agricultural soils, warranting further evaluation of the associated ecological risks of microplastics in soil ecosystems.

The complete mitochondrial genome of an endangered minnow Aphyocypris lini (Cypriniformes: Xenocyprididae): genome characterization and phylogenetic consideration - Zhi Zhang; Shuying Li; Jiling Zhang; Wulin Song; Jin Yang; Jingli Mu (Biologia, 2021)

Using iTRAQ-Based Quantitative Proteomics Analysis to Identify Differentially Expressed Proteins Related to Larval Development of Portunus trituberculatus - Xiayue Chen; Changkao Mu; Ronghua Li; Yangfang Ye; Weiwei Song; Ce Shi; Lei Liu; Huan Wang; Chunlin Wang (Journal of Ocean University of China, 2021)

Correction to: Thirteen-week subcutaneous repeated dose toxicity study of butylparaben and its toxicokinetics in rats - Jin-Sook Bae; Jung Dae Lee; Si-Whan Song; Ho-Chul Shin; Yong-Kyu Choi; Chan Young Shin; Byung-Mu Lee; Kyu-Bong Kim (Archives of Toxicology, 2021)

Thirteen-week subcutaneous repeated dose toxicity study of butylparaben and its toxicokinetics in rats - Jin-Sook Bae; Jung Dae Lee; Si-Whan Song; Ho-Chul Shin; Yong-Kyu Choi; Chan Young Shin; Byung-Mu Lee; Kyu-Bong Kim (Archives of Toxicology, 2021)

The Effects of Lactobacillus plantarum-12 Crude Exopolysaccharides on the Cell Proliferation and Apoptosis of Human Colon Cancer (HT-29) Cells - Mengying Sun; Wenwen Liu; Yinglong Song; Yanfeng Tuo; Guangqing Mu; Fenglian Ma (Probiotics and Antimicrobial Proteins, 2021)

Dissipation kinetics and safety evaluation of pyraclostrobin and its desmethoxy metabolite BF 500-3 in a cucumber greenhouse agroecosystem - Lifei He; Falin He; Song Yang; Yangyang Gao; Beixing Li; Feng Liu; Wei Mu (Environmental Science and Pollution Research, 2021)

Association of FMO3 rs1736557 polymorphism with clopidogrel response in Chinese patients with coronary artery disease - Kong-Xiang Zhu; Pei-Yuan Song; He-Li; Mu-Peng Li; Yin-xiao Du; Qi-lin Ma; Li-Ming Peng; Xiao-Ping Chen (European Journal of Clinical Pharmacology, 2021)

Pseudomonas aeruginosa antitoxin HigA functions as a diverse regulatory factor by recognizing specific pseudopalindromic DNA motifs - Yingjie Song; Guihua Luo; Yibo Zhu; Tao Li; Changcheng Li; Lihui He; Ninglin Zhao; Chang Zhao; Jing Yang; Qin Huang; Xingyu Mu; Xinyue Tang; et al. (Environmental Microbiology, 2021)
Summary Type II toxin‐antitoxin (TA) systems modulate many essential cellular processes in prokaryotic organisms. Recent studies indicate certain type II antitoxins also transcriptionally regulate other genes, besides neutralizing toxin activity. Herein, we investigated the diverse transcriptional repression properties of type II TA antitoxin PaHigA from Pseudomonas aeruginosa . Biochemical and functional analyses showed that PaHigA recognized variable pseudopalindromic DNA sequences and repressed expression of multiple genes. Furthermore, we presented high resolution structures of apo‐PaHigA, PaHigA‐P higBA and PaHigA‐P pa2440 complex, describing how the rearrangements of the HTH domain accounted for the different DNA‐binding patterns among HigA homologues. Moreover, we demonstrated that the N‐terminal loop motion of PaHigA was associated with its apo and DNA‐bound states, reflecting a switch mechanism regulating HigA antitoxin function. Collectively, this work extends our understanding of how the PaHigB/HigA system regulates multiple metabolic pathways to balance the growth and stress response in P. aeruginosa and could guide further development of anti‐TA oriented strategies for pathogen treatment.

Effect of climate change induced extreme precipitation on landslide activity in the Three Gorges Reservoir, China - Dengfeng Zhu; Kun Song; Jingchao Mu; Haifeng Huang; Hongjian Du; Fanzhe Xiazhuang; Chi Sun (Bulletin of Engineering Geology and the Environment, 2021)

High Spatial Resolution and High Temporal Frequency (30-m/15-day) Fractional Vegetation Cover Estimation over China Using Multiple Remote Sensing Datasets: Method Development and Validation - Xihan Mu; Tian Zhao; Gaiyan Ruan; Jinling Song; Jindi Wang; Guangjian Yan; Tim R. Mcvicar; Kai Yan; Zhan Gao; Yaokai Liu; Yuanyuan Wang (Journal of Meteorological Research, 2021)

A high-resolution melting analysis method for the effective discrimination of three Sepia species - Yun Zhao; Weiwei Song; Ronghua Li; Chunlin Wang; Changkao Mu (Journal of Consumer Protection and Food Safety, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Mitigating arsenic accumulation in rice (Oryza sativa L.) using Fe-Mn-La-impregnated biochar composites in arsenic-contaminated paddy soil - Lina Lin; Minling Gao; Zhengguo Song; Haiyan Mu (Environmental Science and Pollution Research, 2020)

A new indole alkaloid with anti-inflammatory from the branches of Nauclea officinalis - Le-Ling Song; Yan-Ling Mu; Hao-Chao Zhang; Gui-Ying Wu; Jing-Yong Sun (Natural Product Research, 2020)

Antimicrobial activity of Curcuma xanthorrhiza nanoemulsions on Streptococcus mutans biofilms - Mu-Yeol Cho; Si-Mook Kang; Eun-Song Lee; Baek-Il Kim (Biofouling, 2020)

An effective method for identification of three mussel species and their hybrids based on SNPs - Xingqiang Chen; Ronghua Li; Chunlin Wang; Changkao Mu; Weiwei Song; Lei Liu; Ce Shi; Pingping Zhan (Conservation Genetics Resources, 2020)

Integration of transcriptomics, proteomics and metabolomics identifies biomarkers for pulmonary injury by polyhexamethylene guanidine phosphate (PHMG-p), a humidifier disinfectant, in rats - Jung Dae Lee; Hyang Yeon Kim; Keunsoo Kang; Hye Gwang Jeong; Mi-Kyung Song; In Hwan Tae; Su Hyun Lee; Hae Ri Kim; Kyuhong Lee; Sehyun Chae; Daehee Hwang; Suhkmann Kim; et al. (Archives of Toxicology, 2020)

Molecular identification reveals hybrids of Mytilus coruscus × Mytilus galloprovincialis in mussel hatcheries of China - Weijia Zhang; Ronghua Li; Xingqiang Chen; Chunlin Wang; Zhongqi Gu; Changkao Mu; Weiwei Song; Pingping Zhan; Ji Huang (Aquaculture International, 2020)

A core set of microsatellite loci for yellow-throated marten, Martes flavigula: a case of inferences of family relationships - Seon-Mi Lee; Hea Chang Moon; Hye Sook Jeon; Eui-Geun Song; Donggul Woo; Junghwa An; Mu-Yeong Lee (Genes & Genomics, 2019)

MicroRNA transcriptome analysis of poly I:C-stimulated and PRRSV-infected porcine alveolar macrophages - Junjing Wu; Ziyun Ji; Mu Qiao; Xianwen Peng; Huayu Wu; Zhongxu Song; Haizhong Zhao; Guisheng Liu; Fenge Li; Shuqi Mei (Journal of Applied Genetics, 2019)

Analysis of DNA Methylation Level of Portunus trituberculatus Subjected to Low Salinity with Methylation-Sensitive Amplification Polymorphism - Shaokun Lu; Ronghua Li; Tianlong Gao; Chunlin Wang; Weibing Zheng; Changkao Mu; Weiwei Song (Journal of Ocean University of China, 2019)

Remote Detection of Varying Water Storage in Relation to Surfacial Temperature of Aral Sea - Guangyi Mu; Li Chen; Liangjun Hu; Kaishan Song (Chinese Geographical Science, 2019)

Use of near-isogenic lines to precisely map and validate a major QTL for grain weight on chromosome 4AL in bread wheat (Triticum aestivum L.) - Panfeng Guan; Na Di; Qing Mu; Xueyi Shen; Yongfa Wang; Xiaobo Wang; Kuohai Yu; Wanjun Song; Yongming Chen; Mingming Xin; Zhaorong Hu; Weilong Guo; et al. (Theoretical and Applied Genetics, 2019)

Effects of water content on the shear behavior and critical state of glacial till in Tianmo Gully of Tibet, China - Gordon G. D. Zhou; Lei-lei Chen; Qing-yi Mu; Kahlil Fredrick E. Cui; Dong-ri Song (Journal of Mountain Science, 2019)

Trade-offs and synergies between seed yield, forage yield, and N-related disservices for a semi-arid perennial grassland under different nitrogen fertilization strategies - Yujie Shi; Junfeng Wang; Xavier Le Roux; Chunsheng Mu; Yunna Ao; Song Gao; Jinwei Zhang; Johannes M. H. Knops (Biology and Fertility of Soils, 2019)

Compression characteristics of saturated re-compacted glacial tills in Tianmo Gully of Tibet, China - Lei-lei Chen; Gordon G. D. Zhou; Qing-yi Mu; Kahlil Fredrick E. Cui; Dong-ri Song (Journal of Mountain Science, 2019)

Genetic analysis of cob resistance to F. verticillioides: another step towards the protection of maize from ear rot - Cong Mu; Jingyang Gao; Zijian Zhou; Zhao Wang; Xiaodong Sun; Xuecai Zhang; Huafang Dong; Yanan Han; Xiaopeng Li; Yabin Wu; Yunxia Song; Peipei Ma; et al. (Theoretical and Applied Genetics, 2019)

Magnetic mineral diagenesis in sediments of saline lake Lop Nur - Wen Li; Gui-jin Mu; Yong-chong Lin; Hao-ze Song (Journal of Mountain Science, 2019)

The features as a county of Chu State: chemical and metallurgical characteristics of the bronze artifacts from the Bayilu site - Di Mu; Wugan Luo; Guoding Song; Baotong Qiao; Fengjian Wang (Archaeological and Anthropological Sciences, 2019)

The bronze artifacts from the Yejiashan site and the political presence of the Zhou dynasty in the middle Yangtze Plain: an application of lead isotope analysis - Di Mu; Wugan Luo; Fengchun Huang; Guoding Song (Archaeological and Anthropological Sciences, 2018)

Drift analysis of MH370 debris in the southern Indian Ocean - Jia Gao; Lin Mu; Xianwen Bao; Jun Song; Yang Ding (Frontiers of Earth Science, 2018)

An Evaluation of the Resilience of the Regional Agricultural Water and Soil Resource System in Heilongjiang Province, China - Dong Liu; Ran Mu; Qiang Fu; Chunlei Liu; Tianxiao Li; Khan M. Imran; Song Cui; Faiz M. Abrar (Agricultural Research, 2018)

Cadmium and lead accumulations and agronomic quality of a newly bred pollution-safe cultivar (PSC) of water spinach - Ying-Ying Huang; Yang-Xiu Mu; Chun-Tao He; Hui-Ling Fu; Xue-Song Wang; Fei-Yue Gong; Zhong-Yi Yang (Environmental Science and Pollution Research, 2018)

The relationship of chromophoric dissolved organic matter parallel factor analysis fluorescence and polycyclic aromatic hydrocarbons in natural surface waters - Sijia Li; Ya’nan Chen; Jiquan Zhang; Kaishan Song; Guangyi Mu; Caiyun Sun; Hanyu Ju; Meichen Ji (Environmental Science and Pollution Research, 2018)

Rapid virulence shift of an H5N2 avian influenza virus during a single passage in mice - Jeong-Hyun Nam; Sang-Mu Shim; Eun-Jung Song; Erica Españo; Dae-Gwin Jeong; Daesub Song; Jeong-Ki Kim (Archives of Virology, 2017)

The immunostimulatory effect of saponin immersion against Vibrio alginolyticus in swimming crab Portunus trituberculatus - Jonas Wiza Ng’ambi; Ronghua Li; Changkao Mu; Weiwei Song; Chunlin Wang (Aquaculture International, 2017)

Chloride Co-transporter NKCC1 Inhibitor Bumetanide Enhances Neurogenesis and Behavioral Recovery in Rats After Experimental Stroke - Wangshu Xu; Xiaopeng Mu; Huibin Wang; Chengguang Song; Wenping Ma; Jukka Jolkkonen; Chuansheng Zhao (Molecular Neurobiology, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

Definition of water exchange zone between the Bohai Sea and Yellow Sea and the effect of winter gale on it - Jun Song; Junru Guo; Jing Li; Lin Mu; Yulong Liu; Guosong Wang; Yan Li; Huan Li (Acta Oceanologica Sinica, 2017)

Associations of sleep duration with metabolic syndrome and its components in adult Koreans: from the Health Examinees Study - Hyung-Suk Yoon; Kyoung-Mu Lee; Jae Jeong Yang; Hwi-Won Lee; Minkyo Song; Sang-Ah Lee; Jong-koo Lee; Daehee Kang (Sleep and Biological Rhythms, 2016)

Baseline sensitivity and control efficacy of antibiosis fungicide tetramycin against Botrytis cinerea - Yingying Song; Leiming He; Lele Chen; Yupeng Ren; Hongbao Lu; Su Geng; Wei Mu; Feng Liu (European Journal of Plant Pathology, 2016)

Effects of light curing modes and ethanol-wet bonding on dentin bonding properties - Mu-zi Li; Jin-rui Wang; Hong Liu; Xia Wang; Kang Gan; Xiu-ju Liu; De-li Niu; Xiao-qing Song (Journal of Zhejiang University-SCIENCE B, 2016)

A novel surfactant-, NaCl-, and protease-tolerant β-mannanase from Bacillus sp. HJ14 - Rui Zhang; Zhifeng Song; Qian Wu; Junpei Zhou; Junjun Li; Yuelin Mu; Xianghua Tang; Bo Xu; Junmei Ding; Shucan Deng; Zunxi Huang (Folia Microbiologica, 2016)

Panobinostat PK/PD profile in combination with bortezomib and dexamethasone in patients with relapsed and relapsed/refractory multiple myeloma - Song Mu; Yoshiaki Kuroda; Hirohiko Shibayama; Masayuki Hino; Takeshi Tajima; Claudia Corrado; Rong Lin; Edward Waldron; Florence Binlich; Kenshi Suzuki (European Journal of Clinical Pharmacology, 2016)

Baseline sensitivity and efficacy of the sterol biosynthesis inhibitor triflumizole against Botrytis cinerea - Yingying Song; Datong Xu; Hongbao Lu; Leiming He; Lele Chen; Junan Shao; Chunmei Xu; Wei Mu; Feng Liu (Australasian Plant Pathology, 2016)

Pyruvate Kinase M2: A Novel Biomarker for the Early Detection of Acute Kidney Injury - Ji Hyun Cheon; Sun Young Kim; Ji Yeon Son; Ye Rim Kang; Ji Hye An; Ji Hoon Kwon; Ho Sub Song; Aree Moon; Byung Mu Lee; Hyung Sik Kim (Toxicological Research, 2016)

Effects of metalloprotease anthrax lethal factor on its peptide-based inhibitor R9LF-1 - Qingsheng Kong; Yuezhang Song; Minlei Mu; Xiaolin Han; Chuanping Si; Feng Li (Molecular and Cellular Biochemistry, 2015)

Desulfurization of immobilized sulfur-oxidizing bacteria, Thialkalivibrio versutus, by magnetic nanaoparticles under haloalkaliphilic conditions - Xiaohui Xu; Yufeng Cai; Ziyu Song; Xiaoling Qiu; Jiemin Zhou; Yilan Liu; Tingzhen Mu; Dan Wu; Yueping Guan; Jianmin Xing (Biotechnology Letters, 2015)

Enriched Environment Altered Aberrant Hippocampal Neurogenesis and Improved Long-Term Consequences After Temporal Lobe Epilepsy in Adult Rats - Xiaoqian Zhang; Tingting Liu; Zhike Zhou; Xiaopeng Mu; Chengguang Song; Ting Xiao; Mei Zhao; Chuansheng Zhao (Journal of Molecular Neuroscience, 2015)

Population pharmacokinetics of intravenous and oral panobinostat in patients with hematologic and solid tumors - Marina Savelieva; Margaret M. Woo; Horst Schran; Song Mu; Jerry Nedelman; Renaud Capdeville (European Journal of Clinical Pharmacology, 2015)

P5-2 of rice black-streaked dwarf virus is a non-structural protein targeted to chloroplasts - Xiao-Ya Liu; Jian Yang; Li Xie; Jing Li; Xi-Jiao Song; Jian-Ping Chen; Heng-Mu Zhang (Archives of Virology, 2015)

Expression screening and annotation of Sepiella maindroni ink sac cDNA library - WEI-WEI SONG; CHANG-KAO MU; SHAO CHU; YU-YU ZHANG; PING-PING ZHAN; CHUN-LIN WANG (Journal of Genetics, 2014)

Isolation and characterization of 42 microsatellite loci from the Hemifusus tuba Gmelin - Lei Wu; Ronghua Li; Chunlin Wang; Changkao Mu; Weiwei Song (Conservation Genetics Resources, 2014)

Characterization of the mitochondrial genome and phylogeny of the black arowana (Osteoglossum ferreirai) - Xidong Mu; Yi Liu; Xuejie Wang; Chao Liu; Hongmei Song; Yinchang Hu; Jianren Luo (Biologia, 2014)

Prognostic significance of TBX2 expression in non-small cell lung cancer - Bo Hu; Hai-Ping Mu; Yu-Qing Zhang; Chong-Yi Su; Jian-Tao Song; Chong Meng; Dong-Xing Liu (Journal of Molecular Histology, 2014)

Occurrence and particle-size distributions of polycyclic aromatic hydrocarbons in the ambient air of coking plant - Xiaofeng Liu; Lin Peng; Huiling Bai; Ling Mu; Chongfang Song (Environmental Geochemistry and Health, 2014)

Suppression of Grb2 expression improved hepatic steatosis, oxidative stress, and apoptosis induced by palmitic acid in vitro partly through insulin signaling alteration - Xiangxiang Shan; Yufeng Miao; Rengen Fan; Changzhi Song; Guangzhou Wu; Zhengqiang Wan; Jian Zhu; Guan Sun; Wenzhang Zha; Xiangming Mu; Guangjun Zhou; Yan Chen (In Vitro Cellular & Developmental Biology - Animal, 2013)

Prelog and anti-Prelog stereoselectivity of two ketoreductases from Candida glabrata - Ping Liang; Bin Qin; Mao Mu; Xin Zhang; Xian Jia; Song You (Biotechnology Letters, 2013)

Development and characterization of EST-derived microsatellite makers for swimming crab, Portunus trituberculatus - Qian Wei; Chunlin Wang; Changkao Mu; Weiwei Song; Ronghua Li (Conservation Genetics Resources, 2013)

Synthesis, physico-chemical properties, and antimicrobial evaluation of a new series of iron(III) hexadentate chelators - Yuan-Yuan Xie; Mu-Song Liu; Pan-Pan Hu; Xiao-Le Kong; Di-Hong Qiu; Ji-Lin Xu; Robert C. Hider; Tao Zhou (Medicinal Chemistry Research, 2013)

Rural tourism development in China: Principles, models and the future - Ling-en Wang; Sheng-kui Cheng; Lin-sheng Zhong; Song-lin Mu; Bijaya G. C. Dhruba; Guo-zhu Ren (Journal of Mountain Science, 2013)

Participatory agroforestry development for restoring degraded sloping land in DPR Korea - Jianchu Xu; Meine van Noordwijk; Jun He; Kwang-Ju Kim; Ryong-Song Jo; Kon-Gyu Pak; Un-Hui Kye; Jong-Sik Kim; Kwon-Mu Kim; Yong-Nam Sim; Je-Un Pak; Ki-Ung Song; et al. (Agroforestry Systems, 2012)

Low-frequency variability of a semi-closed sea induced by the circulation in an adjacent ocean in a wind-driven, quasi-geostrophic, eddy-resolving simulation - Lin Mu; Linhao Zhong; Lijuan Hua; Jun Song (Ocean Dynamics, 2011)

Numerical study of M2 internal tide generation and propagation in the Luzon Strait - Huan Li; Dan Song; Xueen Chen; Hongbao Qian; Lin Mu; Jun Song (Acta Oceanologica Sinica, 2011)

Vertical structure and seasonal variation of tidal and residual currents in the northern Huanghai Sea - Jun Song; Junru Guo; Lulu Qiao; Lin Mu; Zhigang Yao; Yang Liu; Huan Li; Xianwen Bao; Xiaoyan Sun; Jia Gao (Acta Oceanologica Sinica, 2011)

Reproductive failure in wild boars associated to porcine parvovirus infection and in vivo and in vitro characterization of the causal isolate - Chao-fan Zhang; Cui-Ping Song; Chang-mu Chen; Shang-jin Cui; Lan-fei Miao (Tropical Animal Health and Production, 2010)

100 years of Sediment History of Heavy Metals in Daya Bay, China - J. Z. Du; H. D. Mu; H. Q. Song; S. P. Yan; Y. J. Gu; J. Zhang (Water, Air, & Soil Pollution, 2008)

Trace metal concentrations in suspended particles, sediments and clams (Ruditapes philippinarum) from Jiaozhou Bay of China - Yu Li; Zhiming Yu; Xiuxian Song; Qinglin Mu (Environmental Monitoring and Assessment, 2006)

Estimation of Population Pharmacokinetic Parameters in the Presence of Non-compliance - Song Mu; Thomas M. Ludden (Journal of Pharmacokinetics and Pharmacodynamics, 2003)